Adhesive tape with separator

JP2026167454APending Publication Date: 2026-10-14SEKISUI CHEMICAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2026006587
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2026-01-19
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0143】 本発明によれば、粘着テープを貼り合わせる際におけるエア抜け性に優れるセパレータ付き粘着テープを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026167454000001
    Figure 2026167454000001
  • Figure 2026167454000002
    Figure 2026167454000002
  • Figure 2026167454000003
    Figure 2026167454000003
Patent Text Reader

Abstract

To provide an adhesive tape with a separator that offers excellent air release when bonding adhesive tapes together. [Solution] The adhesive tape comprises at least one separator and an adhesive layer, wherein the adhesive layer has a groove-like pattern on the surface in contact with the separator, and when the depth of the grooves in the groove-like pattern on the surface in contact with the separator of the adhesive layer is x (μm) and the thickness of the adhesive layer in contact with the separator is y (μm), the adhesive layer satisfies the following relation (I) or relation (II). (I)0 <x≦5、かつ、x≦y≦8x (II)5
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive tape with a separator.

Background Art

[0002] Conventionally, adhesive tapes having an adhesive layer formed using an adhesive composition have been widely used for fixing components in electronic parts, vehicles, houses and building materials (for example, Patent Documents 1 to 3). Specifically, for example, adhesive tapes are used to bond a cover panel for protecting the surface of portable electronic devices to a touch panel module or a display panel module, or to bond a touch panel module and a display panel module to each other.

Prior Art Documents

Patent Documents

[0003]

Patent Document 1

Patent Document 2

Patent Document 3

Summary of Invention

Problems to be Solved by the Invention

[0004] In recent years, along with the higher performance of electronic devices, the diversification, thinning, and miniaturization of applications of electronic devices have progressed, and the shapes of components and members constituting electronic devices have been made finer and more complex, and adhesive members such as adhesive tapes for bonding and fixing components and members have also been made finer and more complex.

[0005] On the other hand, when bonding an adhesive tape to an adherend, air may be entrapped at the bonding interface, which may cause a problem of impairing bonding reliability. As electronic devices become thinner, the thickness accuracy required of adhesive tapes used in these devices is increasing. When such adhesive tapes are bonded to a substrate, if air is trapped at the adhesive interface, it not only impairs the reliability of the bond but also affects the thickness accuracy. Therefore, adhesive tapes used in thin electronic devices are required to have superior air-releasing properties that prevent air from entering the adhesive interface with the substrate, compared to conventional adhesive tapes.

[0006] The present invention aims to provide an adhesive tape with a separator that offers excellent air release properties when adhesive tapes are bonded together. [Means for solving the problem]

[0007] Disclosure 1 comprises at least one separator and an adhesive tape including an adhesive layer, wherein the adhesive layer has a groove-like pattern on the surface in contact with the separator, and when the depth of the grooves in the groove-like pattern on the surface of the adhesive layer in contact with the separator is x (μm) and the thickness of the adhesive layer in contact with the separator is y (μm), the adhesive layer is an adhesive tape with a separator that satisfies the following relation (I) or relation (II). (I)0 <x≦5、かつ、x≦y≦8x (II)5 <x、かつ、x≦y≦(11 / 5)x+29 Disclosure 2 includes an adhesive tape comprising at least one separator, an adhesive layer and a substrate, wherein the adhesive layer has a groove-like pattern on the surface in contact with the separator, and when the depth of the grooves in the groove-like pattern on the surface of the adhesive layer in contact with the separator is x (μm) and the thickness of the adhesive layer in contact with the separator is y (μm), the adhesive layer satisfies the following relation (I) or relation (II), and the adhesive layer is an adhesive tape with a separator that includes a portion satisfying x = y. (I)0 <x≦5、かつ、x≦y≦8x (II)5 <x、かつ、x≦y≦(11 / 5)x+29 Disclosure 3 is an adhesive tape with a separator according to Disclosure 1 or 2, wherein the pitch of the groove-like pattern in the adhesive layer is greater than 0 μm and 3000 μm or less, the depth of the grooves in the groove-like pattern in the adhesive layer is greater than 0 μm and 40 μm or less, and the width of the grooves in the groove-like pattern in the adhesive layer is 5 μm or more and 200 μm or less. Disclosure 4 comprises at least one separator and an adhesive tape including an adhesive layer, wherein the separator has a ridged pattern on the surface in contact with the adhesive layer, and the adhesive tape with a separator satisfies the following relation (III), relation (IV), or relation (V), where z (μm) is the height of the protrusions in the ridged pattern on the surface of the separator in contact with the adhesive layer and y (μm) is the thickness of the adhesive layer in contact with the separator. (III)0 <z≦3、かつ、(1 / 2)z≦y≦(20 / 3)z (IV)3 <z≦20、かつ、(1 / 2)z≦y≦(53 / 15)z+9.4 (V)20 <z、かつ、z-10≦y≦(53 / 15)z+9.4 Disclosure 5 is an adhesive tape with a separator according to Disclosure 4, wherein the pitch of the ridged pattern on the separator is greater than 0 μm and 3000 μm or less, the height of the protrusions on the ridged pattern on the separator is greater than 0 μm and 40 μm or less, and the width of the protrusions on the ridged pattern on the separator is 5 μm or more and 200 μm or less. Disclosure 6 is further an adhesive tape with a separator according to Disclosure 4 or 5 that satisfies the following relation (VI). (VI) z≦y≦2z Disclosure 7 is an adhesive tape with a separator according to Disclosure 1, 2, 3, 4, 5, or 6, wherein the adhesive layer is a layer formed using an adhesive composition, the adhesive composition contains a base polymer, the adhesive composition contains a (meth)acrylic copolymer having constituent units derived from alkyl (meth)acrylate, and the gel fraction of the adhesive layer is 20% by mass or more. Disclosure 8 is an adhesive tape with a separator according to Disclosure 7, wherein the (meth)acrylic copolymer has structural units derived from alkyl (meth)acrylate having a branched alkyl group, and the content of structural units derived from alkyl (meth)acrylate having a branched alkyl group in the (meth)acrylic copolymer is 50% by mass or more. Disclosure 9 is an adhesive tape with a separator according to Disclosure 7 or 8, wherein the (meth)acrylic copolymer has constituent units derived from alkyl (meth)acrylate having an alkyl group having 4 to 8 carbon atoms, and the content of the constituent units derived from alkyl (meth)acrylate having an alkyl group having 4 to 8 carbon atoms in the (meth)acrylic copolymer is 50% by mass or more. Disclosure 10 is an adhesive tape with a separator according to Disclosure 7, 8, or 9, wherein the (meth)acrylic copolymer has constituent units derived from alkyl (meth)acrylate having an alkyl group having 6 to 8 carbon atoms, and the content of the constituent units derived from alkyl (meth)acrylate having an alkyl group having 6 to 8 carbon atoms in the (meth)acrylic copolymer is 50% by mass or more. Disclosure 11 is an adhesive tape with a separator according to Disclosure 10, wherein the (meth)acrylic copolymer has two or more constituent units derived from alkyl (meth)acrylate having an alkyl group with 6 or more carbon atoms and 8 or fewer carbon atoms. Disclosure 12 is an adhesive tape with a separator according to Disclosure 7, 8, 9, 10, or 11, wherein the (meth)acrylic copolymer has constituent units derived from alkyl (meth)acrylates having a boiling point of 170°C or higher. Disclosure 13 is an adhesive tape with a separator according to Disclosure 7, 8, 9, 10, 11, or 12, wherein the (meth)acrylic copolymer has constituent units derived from alkyl (meth)acrylate, the glass transition temperature (Tg) when it is a homopolymer is -70°C or higher. Disclosure 14 is an adhesive tape with a separator according to Disclosure 7, 8, 9, 10, 11, 12, or 13, wherein the (meth)acrylic copolymer has constituent units derived from biological alkyl (meth)acrylates. Disclosure 15 is an adhesive tape with a separator according to Disclosure 7, 8, 9, 10, 11, 12, 13, or 14, wherein the (meth)acrylic copolymer has constituent units derived from monomers having crosslinkable functional groups, and the content of constituent units derived from monomers having crosslinkable functional groups in the (meth)acrylic copolymer is 0.01% by mass or more and 20% by mass or less. Disclosure 16 is an adhesive tape with a separator according to Disclosure 15, wherein the (meth)acrylic copolymer has constituent units derived from a hydroxyl group-containing monomer, and the content of the constituent units derived from the hydroxyl group-containing monomer in the (meth)acrylic copolymer is 0.01% by mass or more and 2.0% by mass or less. Disclosure 17 is an adhesive tape with a separator according to Disclosure 15 or 16, wherein the (meth)acrylic copolymer has structural units derived from a carboxyl group-containing monomer, and the content of structural units derived from the carboxyl group-containing monomer in the (meth)acrylic copolymer is 0.1% by mass or more and 15% by mass or less. Disclosure 18 is an adhesive tape with a separator according to Disclosure 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, or 17, wherein the (meth)acrylic copolymer has a weight-average molecular weight of 300,000 or more and 1,500,000 or less, and a polydispersity of 7.0 or less. Disclosure 19 is an adhesive tape with a separator according to Disclosures 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, or 18, wherein the adhesive composition further contains a crosslinking agent, and the content of the crosslinking agent per 100 parts by mass of the base polymer is 0.01 parts by mass or more and 10 parts by mass or less. Disclosure 20 is an adhesive tape with a separator according to Disclosure 19, wherein the crosslinking agent comprises at least one selected from the group consisting of isocyanate-based crosslinking agents and epoxy-based crosslinking agents. Disclosure 21 is an adhesive tape with a separator according to Disclosure 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20, wherein the adhesive composition further contains a tackifying resin, and the content of the tackifying resin relative to 100 parts by mass of the base polymer is 10 parts by mass or more and 50 parts by mass or less. Disclosure 22 is an adhesive tape with a separator according to Disclosure 21, wherein the tackifying resin has a softening point of 80°C or more and 170°C or less. Disclosure 23 is an adhesive tape with a separator according to Disclosure 21 or 22, which includes an adhesive resin having a hydroxyl value of 20 mg KOH / g or more and 150 mg KOH / g or less. Disclosure 24 is an adhesive tape with a separator according to Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, or 23, wherein the thickness of at least one of the adhesive layers is 120 μm or less. Disclosure 25 is an adhesive tape with a separator according to Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, or 24, wherein the adhesive layer has a shear storage modulus at 23°C measured by dynamic viscoelastic measurement at a measurement frequency of 10 Hz of 0.1 MPa or more. Disclosure 26 is an adhesive tape with a separator according to Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, or 25, wherein the adhesive layer has a shear storage modulus at 85°C measured by dynamic viscoelastic measurement at a measurement frequency of 10 Hz of 0.02 MPa or more. Disclosure 27 is an adhesive tape with a separator according to Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, or 26, wherein the adhesive layer has a glass transition temperature of 0°C or higher, as measured by dynamic viscoelastic measurement at a measurement frequency of 10 Hz. Disclosure 28 is an adhesive tape with a separator according to Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, or 27, wherein the separator comprises at least one selected from the group consisting of paper and film. Disclosure 29 is an adhesive tape with a separator according to Disclosure 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, or 28, wherein the separator has a resin layer having a ridged pattern, and the resin layer is a layer containing polyethylene. Disclosure 30 is an adhesive tape with separators according to Disclosures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, or 29, wherein the adhesive tape has separators on both sides, and the peeling force when one separator is peeled 180° from the adhesive tape is different from the peeling force when the other separator is peeled 180° from the adhesive tape. The present invention will be described in detail below. Furthermore, the separator-attached adhesive tape according to Disclosure 1 will also be referred to as "separator-attached adhesive tape of the present invention 1," the separator-attached adhesive tape according to Disclosure 2 will also be referred to as "separator-attached adhesive tape of the present invention 2," and the separator-attached adhesive tape according to Disclosure 4 will also be referred to as "separator-attached adhesive tape of the present invention 3." Matters common to the separator-attached adhesive tapes of the present inventions 1 to 3 will not be specifically specified, or will be described as "separator-attached adhesive tape of the present invention."

[0008] In conventional adhesive tapes, one method for obtaining an adhesive tape with excellent air release properties is to use a separator that has a grid-like embossed pattern the same size as the surface of the adhesive layer of the adhesive tape. Specifically, one method involves transferring the shape of the convex parts of the separator, created by the embossing, to the adhesive layer of the adhesive tape, thereby forming a grid-like recess on the surface of the adhesive layer. When an adhesive tape has an adhesive layer formed with a grid-like recess, air escapes from the grid-like recess when it is applied to a substrate, resulting in excellent air release properties.

[0009] On the other hand, when punching an adhesive tape into a target size, it is necessary to perform the processing using a separator larger in size than the adhesive tape for the purposes of protecting the edge of the adhesive layer, improving work efficiency in the production of the adhesive tape, and preventing damage to the edge of the adhesive tape when peeling the separator from the adhesive layer. Therefore, when processing an adhesive tape having grid-shaped recesses on the surface of the adhesive layer as described above, it is necessary to first superimpose a grid-embossed separator on the adhesive layer to form grid-shaped recesses on the surface of the adhesive layer, then replace the embossed separator with a general separator that is not embossed, and then perform punching into a desired size. However, in such a case, there is a problem that the grid of the adhesive layer formed by the grid-embossed separator disappears over time between the replacement of the embossed separator with a general non-embossed separator and the lamination of the produced adhesive tape to an adherend, making it impossible to exhibit sufficient air release properties.

[0010] The present inventors have found that, for an adhesive tape with a separator comprising at least one separator and an adhesive tape including an adhesive layer, when the surface of the adhesive layer in contact with the separator has a groove-shaped pattern, and the depth of the grooves in the groove-shaped pattern of the adhesive layer and the thickness of the adhesive layer satisfy a specific relationship, the adhesive tape with a separator can have excellent air release properties when the adhesive tape is laminated, and have completed the adhesive tape with a separator of the present invention 1. Further, regarding the adhesive tape with a separator of the present invention 1, the present inventors have found that when the adhesive tape includes a base material, and the depth of the grooves in the groove-shaped pattern of the adhesive layer and the thickness of the adhesive layer satisfy a specific relationship, the adhesive tape with a separator can have excellent air release properties when the adhesive tape is laminated, and have completed the adhesive tape with a separator of the present invention 2. Furthermore, the present inventors have found that for an adhesive tape with a separator comprising at least one separator and an adhesive tape including an adhesive layer, when the surface of the separator in contact with the adhesive layer has a ridge-shaped pattern, and the height of the protrusions in the ridge-shaped pattern of the separator and the thickness of the adhesive layer satisfy a specific relationship, the adhesive tape with a separator can exhibit excellent air release performance when the adhesive tape is bonded together, thereby completing the adhesive tape with a separator according to the third aspect of the present invention.

[0011] The adhesive tape with a separator of the present invention comprises at least one separator and an adhesive tape including an adhesive layer. That is, the adhesive tape with a separator may have a separator on one side, or may have separators on both sides. In the above adhesive tape with a separator, the separator is present on the outermost surface.

[0012] Furthermore, the above adhesive tape may be a non-support type tape having no base material, or may be a support type tape having a base material. Furthermore, when the above adhesive tape is a support type tape having a base material, it may be a single-sided adhesive tape having an adhesive layer on one side of the base material, or may be a double-sided adhesive tape having the above adhesive layer on at least one side of the base material. Furthermore, when the above adhesive tape is a double-sided adhesive tape, among the adhesive layers provided on both sides of the adhesive tape, at least one adhesive layer and the separator adjacent to the adhesive layer only need to satisfy the relational formula (I) or (II) described later, or (III), (IV), or (V) described later, and it is preferable that the adhesive layers on both sides satisfy the above configuration.

[0013] The adhesive tapes with separators according to Invention 1 and 2 have a groove-like pattern on the surface of the adhesive layer that contacts the separator, and when the depth of the groove in the groove-like pattern on the surface of the adhesive layer that contacts the separator (hereinafter sometimes simply referred to as "grooves in the adhesive layer") is x (μm) and the thickness of the adhesive layer that contacts the separator is y (μm), the adhesive layer satisfies the following relation (I) or relation (II). (I)0 <x≦5、かつ、x≦y≦8x (II)5 <x、かつ、x≦y≦(11 / 5)x+29 In the separator-equipped adhesive tapes of the present invention 1 and 2, the adhesive layer has a groove-like pattern on the surface in contact with the separator, and satisfies the above relation (I) or above relation (II), thereby making it possible to obtain a separator-equipped adhesive tape with excellent air release properties when adhesive tapes are bonded together. Furthermore, in the adhesive tape with separator according to the present invention 3, it is preferable that the adhesive layer has a groove-like pattern on the surface in contact with the separator, and that the adhesive layer satisfies the above relation (I) or the above relation (II). In the adhesive tape with separator according to the present invention 3, a groove-like pattern is formed on the surface of the adhesive layer in contact with the separator, and the above relation (I) or the above relation (II) is satisfied, thereby making it possible to make an adhesive tape with separator that has superior air release properties when adhesive tapes are bonded together.

[0014] In this specification, the term "grooved pattern" in an adhesive layer means a structure in which the grooves are formed continuously and parallel to each other when the adhesive layer is observed from the grooved side. Furthermore, in this specification, "depth of grooves in the adhesive layer" means the difference obtained by subtracting the thickness of the smallest part of the groove-like pattern from the thickness of the adhesive layer.

[0015] Methods for satisfying the above relational equations (I) and (II) include adjusting the depth of the grooves in the groove-like pattern on the surface in contact with the separator, adjusting the thickness of the adhesive layer in contact with the separator, and forming a ridge-like pattern on the separator and transferring it to the adhesive layer. Therefore, by performing methods such as adjusting the depth of the grooves in the groove-like pattern on the surface in contact with the separator, as described later, the above relations (I) and (II) can be satisfied.

[0016] The lower limit of the groove depth in the adhesive layer described above is not particularly limited and can be greater than 0 μm, but from the viewpoint of improving air release, a preferred lower limit is 2 μm, a more preferred lower limit is 4 μm, and an even more preferred lower limit is 5.5 μm. Furthermore, the preferred upper limit for the groove depth in the adhesive layer is 40 μm. Since a groove depth of 40 μm or less in the adhesive layer allows for the use of a thinner adhesive layer, the resulting separator-equipped adhesive tape can be more suitably used for thin electronic devices. A more preferred upper limit for the groove depth in the adhesive layer is 35 μm, and an even more preferred upper limit is 30 μm.

[0017] The pitch of the groove-like pattern in the adhesive layer is preferably greater than 0 μm and 3000 μm or less. A pitch of the groove-like pattern in the adhesive layer greater than 0 μm increases the adhesion area of ​​the adhesive tape to the adherend, thereby improving the adhesive strength of the adhesive tape. A pitch of the groove-like pattern in the adhesive layer of 3000 μm or less allows air to escape more easily from the adhesive layer, resulting in an adhesive tape with a separator that has superior air release properties when the adhesive tapes are bonded together. A more preferable lower limit for the pitch of the groove-like pattern in the adhesive layer is 200 μm, a more preferable upper limit is 2000 μm, an even more preferable lower limit is 400 μm, and an even more preferable upper limit is 1500 μm.

[0018] In this specification, the "pitch of groove-like patterns" in the adhesive layer refers to the spacing between grooves obtained from the surface of the grooved adhesive layer. The pitch of groove-like patterns may be constant or random, but from the viewpoint of reducing variations in air release within the surface, it is preferable that the pitch of groove-like patterns be constant.

[0019] The groove width in the adhesive layer described above has a preferred lower limit of 5 μm and a preferred upper limit of 200 μm. When the groove width in the adhesive layer is 5 μm or more, air can escape more easily from the adhesive layer, so the resulting adhesive tape with separator has better air release properties when the adhesive tapes are bonded together. When the groove width in the adhesive layer is 200 μm or less, the adhesion area of ​​the adhesive tape to the substrate is increased, so the adhesive strength of the adhesive tape is further improved. A more preferred lower limit for the groove width in the adhesive layer is 18 μm, a more preferred upper limit is 140 μm, an even more preferred lower limit is 23 μm, and an even more preferred upper limit is 100 μm.

[0020] In this specification, "groove width" in the adhesive layer means the width of the groove itself, measured at a position half the depth of the groove in the adhesive layer (groove depth / 2).

[0021] Preferably, the adhesive layer has a groove-like pattern with a pitch greater than 0 μm and 3000 μm or less, a groove depth greater than 0 μm and 40 μm or less, and a groove width of 5 μm or more and 200 μm or less. By satisfying the above configuration, the adhesive layer can be made into an adhesive tape with a separator that has superior air release properties when adhesive tapes are bonded together.

[0022] Methods for adjusting the depth of the grooves in the adhesive layer include, for example, adjusting the hardness of the adhesive layer (specifically, for example, adjusting the type and content of constituent unit monomers in the (meth)acrylic copolymer contained in the adhesive layer, adjusting the type and content of tackifying resin contained in the adhesive layer, adjusting the shear storage modulus of the adhesive layer at 23°C, adjusting the glass transition temperature of the adhesive layer, adjusting the gel fraction of the adhesive layer, etc.), forming a ridged pattern on the separator, adjusting the height of the protrusions, and transferring it to the adhesive layer.

[0023] Methods for adjusting the pitch of the groove-like pattern in the adhesive layer and the width of the grooves in the adhesive layer include, for example, adjusting the hardness of the adhesive layer (specifically, for example, adjusting the type and content of constituent unit monomers in the (meth)acrylic copolymer contained in the adhesive layer, adjusting the type and content of tackifying resin contained in the adhesive layer, adjusting the shear storage modulus of the adhesive layer at 23°C, adjusting the glass transition temperature of the adhesive layer, adjusting the gel fraction of the adhesive layer, etc.), forming a ridge-like pattern on the separator, adjusting the pitch of the ridge-like pattern and the width of the protrusions in the ridge-like pattern, and transferring them to the adhesive layer, etc.

[0024] In relation (I) or (II) above, the thickness of the adhesive layer in contact with the separator is not particularly limited as long as relation (I) or (II) is satisfied. However, a thicker layer can improve the reliability of adhesion. On the other hand, if the thickness is too thick relative to the depth of the grooves formed in the adhesive layer, it will impair air release. Therefore, it is preferable to adjust the thickness in consideration of the application and balance.

[0025] The adhesive layer has a groove-like pattern on the surface in contact with the separator, and if the above relation (I) or (II) is satisfied, the adhesive tape further includes a base material, and it is preferable that the adhesive layer includes a portion satisfying x=y, where x (μm) is the depth of the groove in the groove-like pattern on the surface of the adhesive layer in contact with the separator, and y (μm) is the thickness of the adhesive layer in contact with the separator. Even if the adhesive tape with separator has such a structure, it is possible to make an adhesive tape with separator that has superior air release properties when bonding the adhesive tapes together. Furthermore, an adhesive tape comprising at least one separator, an adhesive layer and a substrate, wherein the adhesive layer has a groove-like pattern on the surface in contact with the separator, and when the depth of the grooves in the groove-like pattern on the surface in contact with the separator of the adhesive layer is x (μm) and the thickness of the adhesive layer in contact with the separator is y (μm), the adhesive layer satisfies the above relation (I) or relation (II), and the adhesive layer includes a portion that satisfies x = y is also one of the disclosures (adhesive tape with separator of the present invention 2).

[0026] The adhesive tape with separator according to the present invention 3 is characterized in that the separator has a ridged pattern on the surface in contact with the adhesive layer, and when the height of the protrusions in the ridged pattern on the surface of the separator in contact with the adhesive layer is z (μm) and the thickness of the adhesive layer in contact with the separator is y (μm), the following relation (III), relation (IV), or relation (V) is satisfied. (III)0 <z≦3、かつ、(1 / 2)z≦y≦(20 / 3)z (IV)3 <z≦20、かつ、(1 / 2)z≦y≦(53 / 15)z+9.4 (V)20 <z、かつ、z-10≦y≦(53 / 15)z+9.4 In the separator-equipped adhesive tape of the present invention 3, the separator has a ridged pattern on the surface in contact with the adhesive layer, and by satisfying the above relation (III), relation (IV), or relation (V), it becomes possible to make a separator-equipped adhesive tape that has excellent air release properties when adhesive tapes are bonded together. Furthermore, in the separator-equipped adhesive tapes of the present invention 1 and 2, it is preferable that the separator has a ridged pattern on the surface in contact with the adhesive layer and satisfies the above-mentioned relation (III), relation (IV), or relation (V). In the separator-equipped adhesive tapes of the present invention 1 and 2, by having a ridged pattern on the surface in contact with the adhesive layer and satisfying the above-mentioned relation (III), relation (IV), or relation (V), it becomes possible to make a separator-equipped adhesive tape with superior air release properties when bonding adhesive tapes together.

[0027] In this specification, the term "ridged pattern" in a separator means a structure in which certain shapes constituting the protrusions are continuously and parallel to each other when observed from the side of the separator that has the protrusions. In this specification, "height of the protrusions in the separator" means the difference between the thickness of the thickest part of the protrusions in the ridged pattern of the separator and the thickness of the thinnest part of the separator.

[0028] Methods for satisfying the above relation (III), relation (IV), or relation (V) include adjusting the height of the protrusions in the ridged pattern on the surface of the separator that is in contact with the adhesive layer, and adjusting the thickness of the adhesive layer that is in contact with the separator. Therefore, by performing a method such as adjusting the height of the protrusions in the ridged pattern on the surface of the separator in contact with the adhesive layer, as described later, the above relation (III), relation (IV), or relation (V) can be satisfied.

[0029] The lower limit of the height of the protrusions in the above separator is not particularly limited and should be greater than 0 μm; however, from the viewpoint of improving air release, a preferred lower limit is 4 μm, and a more preferred lower limit is 7 μm. Furthermore, the height of the protrusions in the separator has a preferred upper limit of 40 μm. Since the height of the protrusions in the separator is 40 μm or less, it becomes possible to use a thinner adhesive layer, and the resulting adhesive tape with separator can be more suitably used for thin electronic devices. A more preferred upper limit for the height of the protrusions in the separator is 37 μm, and an even more preferred upper limit is 32 μm.

[0030] The pitch of the ridged pattern in the separator is preferably greater than 0 μm and 3000 μm or less. A pitch greater than 0 μm in the ridged pattern of the separator allows air to escape more easily from the adhesive layer, resulting in a separator-attached adhesive tape with superior air release properties when the adhesive tapes are bonded together. A more preferable lower limit for the pitch of the ridged pattern in the separator is 200 μm, a more preferable upper limit is 2000 μm, an even more preferable lower limit is 400 μm, and an even more preferable upper limit is 1500 μm.

[0031] In this specification, the "pitch of the ridge pattern" in a separator refers to the distance between the highest points of the protrusions of adjacent separators. The pitch of the ridge pattern may be constant or random, but from the viewpoint of reducing variations in air release within the plane, it is preferable that the pitch of the ridge pattern be constant.

[0032] The width of the protrusions in the separator described above has a preferred lower limit of 5 μm and a preferred upper limit of 200 μm. When the width of the protrusions in the separator described above is 5 μm or more, air can escape more easily from the adhesive layer, so the adhesive tape with the separator that is obtained has better air release properties when the adhesive tapes are bonded together. When the width of the ridge-like protrusions in the separator described above is 200 μm or less, the adhesion area of ​​the adhesive tape to the adherend is increased, so the adhesive strength of the adhesive tape is further improved. A more preferred lower limit for the width of the protrusions in the separator described above is 20 μm, a more preferred upper limit is 170 μm, an even more preferred lower limit is 30 μm, and an even more preferred upper limit is 130 μm.

[0033] In this specification, the "width of the protrusion" in a separator means the width at a position half the height of the protrusion of the separator (height of the protrusion / 2).

[0034] Preferably, the separator has a ridged pattern with a pitch greater than 0 μm and 3000 μm or less, a protrusion height greater than 0 μm and 40 μm or less, and a protrusion width of 5 μm or more and 200 μm or less. By satisfying the above configuration, the ridged pattern of the separator can be made into an adhesive tape with a separator that has superior air release properties when adhesive tapes are bonded together.

[0035] As an example of adjusting the height of the protrusions in the ridged pattern on the surface of the separator that is in contact with the adhesive layer, one method is to adjust the depth of the plate used for shaping the resin that is shaped to form the protrusions on the base film constituting the separator.

[0036] Methods for adjusting the pitch of the ridged pattern in the separator and the width of the protrusions in the separator include, for example, adjusting the depth of the plate used for shaping the resin that forms the protrusions on the base film constituting the separator.

[0037] In relation (III), relation (IV), or relation (V) above, the thickness of the adhesive layer in contact with the separator is not particularly limited as long as it satisfies relation (III), relation (IV), or relation (V). However, a thicker layer can improve the reliability of adhesion. On the other hand, if the thickness is too thick relative to the depth of the grooves formed in the adhesive layer, it will impair air release. Therefore, it is preferable to adjust the thickness in consideration of the application and balance.

[0038] The above-mentioned adhesive tape with separator preferably satisfies the following relation (VI) if the separator has a ridged pattern on the surface in contact with the adhesive layer and satisfies relation (III), relation (IV), or relation (V). (VI) z≦y≦2z By satisfying the above relation (VI), the above-mentioned adhesive tape with separator can be made into an adhesive tape with separator that has superior air release properties when adhesive tapes are bonded together.

[0039] The above-mentioned adhesive tape with separator is preferable if the separator has a ridged pattern on the surface in contact with the adhesive layer and satisfies relation (III), relation (IV), or relation (V), and further satisfies the following relation (VII). (VII) z≦y≦w z: Height (μm) of the protrusions in the ridged pattern on the surface of the separator in contact with the adhesive layer. w: Thickness of the adhesive layer immediately after coating (μm) Because the above-mentioned adhesive tape with separator satisfies the above relation (VII), when manufacturing the adhesive tape including the substrate, the adhesive solution can be easily transferred to the substrate after being applied to the separator. As a result, the adhesive layer and the substrate are sufficiently pressed together, reducing the risk of the adhesive layer detaching from the substrate layer when peeling the separator from the adhesive tape.

[0040] In this specification, "thickness of the adhesive layer immediately after coating" refers to the thickness of the layer after coating with the adhesive solution, and includes the thickness of the solvent and solid matter.

[0041] The above adhesive tape has an adhesive layer. In the adhesive tapes with separators according to the present invention 1 and 2, the adhesive layer has a grooved pattern. Because the adhesive layer has a grooved pattern, air escapes from the grooves when the adhesive tape is adhered to a substrate, resulting in an adhesive tape with a separator that exhibits excellent air release properties when the adhesive tape is adhered. Furthermore, in the adhesive tape with separator according to the present invention 3, it is preferable that the adhesive layer has a groove-like pattern that fits into the ridge-like pattern of the separator. Having such a groove-like pattern in the adhesive layer makes it easier for air to escape from the grooves when the adhesive tape is adhered to the substrate, so that the resulting adhesive tape with separator has superior air release properties when the adhesive tape is adhered.

[0042] Methods for forming groove-like patterns in the adhesive layer include: a method of forming groove-like patterns by transferring the ridge-like pattern from the separator to the adhesive layer by overlapping a separator having a ridge-like pattern onto the adhesive layer during the manufacture of adhesive tape with a separator; a method of forming groove-like patterns by stamp printing when forming a dot-type adhesive as the adhesive layer; and a method of forming groove-like patterns by replacing the separator of an adhesive tape manufactured with a separator that does not have a ridge-like pattern with a separator that has a ridge-like pattern, and then applying pressure.

[0043] The shape of the grooves in the groove-like pattern of the adhesive layer described above is not particularly limited, but examples include trapezoidal, semicircular, rectangular, etc., when viewed in cross-section.

[0044] Preferably, the adhesive layer is a layer formed using an adhesive composition. By forming the adhesive layer using an adhesive composition, it becomes easier to adjust the adhesive layer to an appropriate hardness, making it easier to satisfy the above-mentioned relation (I), relation (II), relation (III), relation (IV), or relation (V). Furthermore, even when the separator is replaced during die-cutting of the adhesive tape into a desired shape, the groove-like pattern of the adhesive layer is less likely to disappear. Therefore, it becomes easier to manufacture adhesive tapes with separators that exhibit superior air release properties when bonding adhesive tapes together. A method for forming the adhesive layer using the above-mentioned adhesive composition includes, for example, applying the adhesive composition to a release film or the like, and then heating and drying the adhesive composition.

[0045] The above adhesive composition preferably contains a base polymer. Examples of the above-mentioned base polymers include (meth)acrylic copolymers having structural units derived from alkyl (meth)acrylates, rubber resins, etc., and among these, from the viewpoint of the thickness of the adhesive layer and the breadth of design, it is preferable that the above-mentioned adhesive composition contains a (meth)acrylic copolymer having structural units derived from alkyl (meth)acrylates as the base polymer. In this specification, "(meth)acrylic" means acrylic or methacrylic, and "(meth)acrylate" means acrylate or methacrylate.

[0046] From the viewpoint of making the adhesive layer easier to obtain, it is preferable that the (meth)acrylic copolymer contains, as a constituent unit derived from the alkyl (meth)acrylate, a constituent unit derived from an alkyl (meth)acrylate having a branched alkyl group (hereinafter sometimes simply referred to as "alkyl (meth)acrylate (a)").

[0047] Examples of constituent units derived from the alkyl(meth)acrylate(a) mentioned above include isobutyl(meth)acrylate, isoamyl(meth)acrylate, 1-methylheptyl(meth)acrylate, 1-methylheptyl(meth)acrylate, isodecyl(meth)acrylate, isostearyl(meth)acrylate, and the like. Among these, constituent units derived from 1-methylheptyl(meth)acrylate are preferred from the viewpoint of making it easier to adjust the shear storage modulus at 23°C, as measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz described later for the adhesive layer, to 0.1 MPa or higher.

[0048] The preferred lower limit for the content of the constituent units derived from the alkyl (meth)acrylate (a) in the above (meth)acrylic copolymer is 50% by mass. When the content of the constituent units derived from the alkyl (meth)acrylate (a) is 50% by mass or more, the adhesive layer tends to become harder and the groove-like pattern formed on the adhesive layer becomes less likely to disappear, so the adhesive tape with separator has better air release properties when adhesive tapes are bonded together. A more preferred lower limit for the content of the constituent units derived from the alkyl (meth)acrylate (a) is 60% by mass, an even more preferred lower limit is 70% by mass, and an even more preferred lower limit is 80% by mass. Furthermore, the preferred upper limit for the content of the constituent units derived from the alkyl (meth)acrylate (a) is 98% by mass. By having a content of 98% by mass or less of the constituent units derived from the alkyl (meth)acrylate (a), the adhesive layer does not become too hard and has appropriate wettability, and even if the adhesive layer has a groove-like pattern, the adhesive tape can ensure more sufficient adhesive reliability. A more preferred upper limit for the content of the constituent units derived from the alkyl (meth)acrylate (a) is 95% by mass, and an even more preferred upper limit is 92% by mass.

[0049] In this specification, the content ratio of constituent units in the (meth)acrylic copolymer is determined by mass spectrometry of the (meth)acrylic copolymer and1 The content can be calculated by performing 1H-NMR measurements and determining the integral intensity ratio of the hydrogen peaks originating from the constituent monomers that make up the constituent units to be measured. Furthermore, if the proportion of constituent monomers in the above (meth)acrylic copolymer is known, that proportion may be used as the content ratio.

[0050] From the viewpoint of the adhesive layer exhibiting appropriate adhesive properties, it is preferable that the (meth)acrylic copolymer contains, as a constituent unit derived from the alkyl (meth)acrylate, an alkyl (meth)acrylate having an alkyl group with 4 to 8 carbon atoms (hereinafter sometimes simply referred to as "alkyl (meth)acrylate (b)").

[0051] Examples of constituent units derived from the alkyl(meth)acrylate(b) above include those derived from n-butyl(meth)acrylate, isobutyl(meth)acrylate, t-butyl(meth)acrylate, n-pentyl(meth)acrylate, isopentyl(meth)acrylate, n-hexyl(meth)acrylate, n-heptyl(meth)acrylate, n-octyl(meth)acrylate, 1-methylheptyl(meth)acrylate, etc. In particular, from the viewpoint of making it easier to adjust the shear storage modulus at 23°C, measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz described later for the adhesive layer, to 0.1 MPa or higher, it is preferable that the (meth)acrylic copolymer contains constituent units derived from alkyl(meth)acrylate having an alkyl group with 6 to 8 carbon atoms (hereinafter sometimes simply referred to as "alkyl(meth)acrylate(c)").

[0052] The preferred lower limit for the content of the constituent units derived from the alkyl(meth)acrylate(b) in the above (meth)acrylic copolymer is 50% by mass. When the content of the constituent units derived from the alkyl(meth)acrylate(b) is 50% by mass or more, the adhesive layer tends to become harder and the groove-like pattern formed on the adhesive layer becomes less likely to disappear, so the adhesive tape with separator has better air release properties when adhesive tapes are bonded together. A more preferred lower limit for the content of the constituent units derived from the alkyl(meth)acrylate(b) is 60% by mass, and an even more preferred lower limit is 70% by mass. Furthermore, the preferred upper limit for the content of the constituent units derived from the alkyl (meth)acrylate (b) is 98% by mass. By having a content of 98% by mass or less of the constituent units derived from the alkyl (meth)acrylate (b), the adhesive layer does not become too hard and has appropriate wettability, and even if the adhesive layer has a groove-like pattern, the adhesive tape can ensure more sufficient adhesive reliability. A more preferred upper limit for the content of the constituent units derived from the alkyl (meth)acrylate (b) is 95% by mass, and an even more preferred upper limit is 92% by mass.

[0053] The preferred lower limit for the content of the constituent units derived from the alkyl (meth)acrylate (c) in the above (meth)acrylic copolymer is 50% by mass. When the content of the constituent units derived from the alkyl (meth)acrylate (c) is 50% by mass or more, the adhesive layer tends to become harder, and the groove-like pattern formed on the adhesive layer becomes less likely to disappear, so the adhesive tape with separator has better air release properties when adhesive tapes are bonded together. A more preferred lower limit for the content of the constituent units derived from the alkyl (meth)acrylate (c) is 60% by mass, and an even more preferred lower limit is 70% by mass. Furthermore, the preferred upper limit for the content of the constituent units derived from the alkyl (meth)acrylate (c) is 98% by mass. By having a content of 98% by mass or less of the constituent units derived from the alkyl (meth)acrylate (c), the adhesive layer does not become too hard and has appropriate wettability, and even if the adhesive layer has a groove-like pattern, the adhesive tape can ensure more sufficient adhesive reliability. A more preferred upper limit for the content of the constituent units derived from the alkyl (meth)acrylate (c) is 95% by mass, and an even more preferred upper limit is 92% by mass. Furthermore, from the viewpoint of making it easier to adjust the glass transition temperature of the adhesive layer, as measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz described later, to 0°C or higher, it is more preferable that the (meth)acrylic copolymer has two or more constituent units derived from the alkyl (meth)acrylate (c), and that the content ratio of the constituent units derived from the alkyl (meth)acrylate (c) in the (meth)acrylic copolymer is 50% by mass or more.

[0054] From the viewpoint of ensuring that the adhesive layer has an appropriate hardness, it is preferable that the (meth)acrylic copolymer has a constituent unit derived from the alkyl (meth)acrylate, which has a boiling point of 170°C or higher (hereinafter sometimes simply referred to as "alkyl (meth)acrylate (d)"). The boiling point of the alkyl (meth)acrylate (d) is more preferably 190°C and even more preferably 200°C. Furthermore, from the viewpoint of preventing the adhesive layer from becoming too hard, the boiling point of the alkyl (meth)acrylate (d) is preferably 270°C and more preferably 250°C. In this specification, "boiling point of alkyl (meth)acrylate" refers to the boiling point at 101 kPa.

[0055] Examples of constituent units derived from the alkyl (meth)acrylate (d) include those derived from n-hexyl acrylate (boiling point: 195°C), n-heptyl acrylate (boiling point: 222°C), n-heptyl methacrylate (boiling point: 229°C), 1-methylheptyl acrylate (boiling point: 218°C), 2-ethylhexyl acrylate (boiling point: 215°C), and 2-ethylhexyl methacrylate (boiling point: 214°C). Among these, constituent units derived from 1-methylheptyl acrylate are preferred from the viewpoint of making it easier to adjust the glass transition temperature, which is measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz described later for the adhesive layer, to 0°C or higher.

[0056] In the above (meth)acrylic copolymer, the preferred lower limit of the content of the constituent units derived from the alkyl (meth)acrylate (d) is 65% by mass, and the preferred upper limit is 98% by mass. When the content of the constituent units derived from the alkyl (meth)acrylate (d) is 65% by mass or more, the adhesive layer tends to become harder, and the groove-like pattern formed on the adhesive layer becomes less likely to disappear, so the adhesive tape with separator has better air release properties when adhesive tapes are bonded together. When the content of the constituent units derived from the alkyl (meth)acrylate (d) is 98% by mass or less, the adhesive layer does not become too hard and has appropriate wettability, and even when the adhesive layer has a groove-like pattern, the adhesive tape can ensure more sufficient adhesive reliability. The more preferable lower limit for the content of the constituent units derived from the alkyl (meth)acrylate (d) is 75% by mass, the more preferable upper limit is 95% by mass, the even more preferable lower limit is 80% by mass, and the even more preferable upper limit is 92% by mass.

[0057] From the viewpoint of making the adhesive layer easier to handle, it is preferable that the (meth)acrylic copolymer has a constituent unit derived from the alkyl (meth)acrylate, which has a glass transition temperature (hereinafter sometimes simply referred to as "homopolymer Tg") of -70°C or higher when it is in homopolymer form (hereinafter sometimes simply referred to as "alkyl (meth)acrylate (e)"). A more preferable lower limit for the glass transition temperature when the alkyl (meth)acrylate (e) is in homopolymer form is -70°C, and an even more preferable lower limit is -60°C. Furthermore, when the above alkyl (meth)acrylate (e) is used as a homopolymer, the glass transition temperature should preferably have an upper limit of 0°C and a more preferably upper limit of -30°C, from the viewpoint of preventing the adhesive layer from becoming too hard. In this specification, "glass transition temperature of homopolymer" refers to the glass transition temperature of a homopolymer in which the alkyl (meth)acrylate has a weight-average molecular weight of 100,000 to 2,000,000, measured by differential scanning calorimetry. The glass transition temperature of the homopolymer can be measured, for example, under a nitrogen atmosphere (nitrogen flow, flow rate 50 mL / min) using a differential scanning calorimeter (Seiko Instruments, "220C", etc.) in accordance with JIS K6240:2011, with a measurement temperature of -100°C to 200°C and a heating rate of 10°C / min.

[0058] Examples of constituent units derived from the alkyl (meth)acrylate(e) mentioned above include those derived from n-butyl acrylate (glass transition temperature when homopolymerized: -54°C), n-hexyl acrylate (glass transition temperature when homopolymerized: -65°C), n-heptyl acrylate (glass transition temperature when homopolymerized: -68°C), and 1-methylheptyl acrylate (glass transition temperature when homopolymerized: -45°C). Among these, constituent units derived from 1-methylheptyl acrylate are preferred from the viewpoint of making it easier to adjust the glass transition temperature, which is measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz described later for the adhesive layer, to 0°C or higher.

[0059] The preferred lower limit and upper limit of the content of the constituent units derived from the alkyl(meth)acrylate(e) in the above (meth)acrylic copolymer is 65% by mass. When the content of the constituent units derived from the alkyl(meth)acrylate(e) is 65% by mass or more, the adhesive layer becomes harder and the groove-like pattern formed on the adhesive layer becomes less likely to disappear, so the adhesive tape with separator has better air release properties when the adhesive tapes are bonded together. When the content of the constituent units derived from the alkyl(meth)acrylate(e) is 98% by mass or less, the adhesive layer does not become too hard and has appropriate wettability, so even when the adhesive layer has a groove-like pattern, the adhesive tape can ensure more sufficient adhesive reliability. The more preferable lower limit for the content of the constituent units derived from the alkyl (meth)acrylate (e) is 75% by mass, the more preferable upper limit is 95% by mass, the even more preferable lower limit is 80% by mass, and the even more preferable upper limit is 92% by mass.

[0060] The constituent units derived from the alkyl (meth)acrylate described above may include constituent units derived from other alkyl (meth)acrylates other than the alkyl (meth)acrylate (a), alkyl (meth)acrylate (b), alkyl (meth)acrylate (c), alkyl (meth)acrylate (d), and alkyl (meth)acrylate (e).

[0061] The constituent units derived from the alkyl (meth)acrylate may consist only of constituent units derived from petroleum-derived materials, but it is preferable that they include constituent units derived from bio-derived alkyl (meth)acrylate containing bio-derived carbon. That is, it is preferable that the (meth)acrylic copolymer has constituent units derived from bio-derived alkyl (meth)acrylate as constituent units derived from the alkyl (meth)acrylate. In recent years, the depletion of petroleum resources and the emission of carbon dioxide from the combustion of petroleum-derived products have become serious concerns. Therefore, attempts are being made to conserve petroleum resources by using bio-based materials instead of petroleum-derived materials. The above alkyl (meth)acrylate is preferable from the viewpoint of conserving petroleum resources because it contains constituent units derived from bio-based materials. Furthermore, since bio-based materials are originally produced by taking in carbon dioxide from the atmosphere, it is thought that burning them will not increase the total amount of carbon dioxide in the atmosphere, which is also preferable from the viewpoint of reducing carbon dioxide emissions.

[0062] When the alkyl(meth)acrylate in the above-mentioned alkyl(meth)acrylate-derived structural unit includes structural units derived from biological materials, it is preferable that the alkyl(meth)acrylate is synthesized by esterification of an alcohol, which is a biological material, with (meth)acrylic acid. One method for obtaining the above-mentioned bio-derived alcohol is to crack ricinoleic acid derived from castor oil to obtain a mixture containing undecylenic acid and n-heptyl alcohol. Then, by separating the undecylenic acid from the resulting mixture by distillation, one can obtain n-heptyl alcohol containing bio-derived carbon. Alternatively, n-heptyl acrylate containing bio-derived carbon can be prepared by esterifying the n-heptyl alcohol containing bio-derived carbon with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.).

[0063] The (meth)acrylic copolymer preferably has structural units derived from monomers having crosslinkable functional groups. The presence of structural units derived from monomers having crosslinkable functional groups in the (meth)acrylic copolymer makes it easier for the adhesive layer to form a crosslinked structure, resulting in a harder adhesive layer, which in turn makes the groove-like pattern formed on the adhesive layer less likely to disappear. As a result, the adhesive tape with separator exhibits superior air release properties when the adhesive tapes are bonded together.

[0064] In the above (meth)acrylic copolymer, the preferred lower limit for the content of constituent units derived from the monomer having the crosslinkable functional group is 0.01% by mass, and the preferred upper limit is 20% by mass. When the content of constituent units derived from the monomer having the crosslinkable functional group is within the above range, the adhesive layer tends to have appropriate hardness, the groove-like pattern formed on the adhesive layer is less likely to disappear, and even when the adhesive layer has a groove-like pattern, it exhibits appropriate wettability, and the adhesive tape can ensure more sufficient adhesive reliability. Furthermore, because the adhesive layer is more likely to form a crosslinked structure, it has appropriate bulk strength, and the resulting adhesive tape has better handling properties. A more preferred lower limit for the content of constituent units derived from the monomer having the crosslinkable functional group is 0.05% by mass, a more preferred upper limit is 10% by mass, an even more preferred lower limit is 0.1% by mass, and an even more preferred upper limit is 7.0% by mass.

[0065] Examples of monomers having the above-mentioned crosslinkable functional group include hydroxyl group-containing monomers, carboxyl group-containing monomers, glycidyl group-containing monomers, amide group-containing monomers, and nitrile group-containing monomers. In particular, since it is easy to adjust the degree of crosslinking of the adhesive layer, it is preferable that the monomer having the above-mentioned crosslinkable functional group includes at least one selected from the group consisting of hydroxyl group-containing monomers and carboxyl group-containing monomers. Furthermore, the monomer having the above-mentioned crosslinkable functional group preferably has a (meth)acryloyl group. In this specification, "(meth)acryloyl" means acryloyl or methacryloyl.

[0066] Examples of the above-mentioned hydroxyl group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 1-methyl-2-hydroxyethyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 1-methyl-2-hydroxypropyl (meth)acrylate, 1-methyl-3-hydroxypropyl (meth)acrylate, 1-ethyl-2-hydroxyethyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 7-hydroxyheptyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, and 9-hydroxynonyl (meth)acrylate. Examples of the above-mentioned carboxyl group-containing monomers include (meth)acrylic acid. Examples of the above-mentioned glycidyl group-containing monomers include glycidyl (meth)acrylate. Examples of the above-mentioned amide group-containing monomers include dimethyl(meth)acrylamide, isopropyl(meth)acrylamide, and dimethylaminopropyl(meth)acrylamide. Examples of the above-mentioned nitrile group-containing monomers include (meth)acrylonitrile.

[0067] In the above (meth)acrylic copolymer, the preferred lower limit of the content of constituent units derived from the above hydroxyl group-containing monomer is 0.01% by mass, and the preferred upper limit is 2.0% by mass. When the content of constituent units derived from the above hydroxyl group-containing monomer is within the above range, the adhesive layer tends to have appropriate hardness, the groove-like pattern formed on the adhesive layer becomes less likely to disappear, and even when the adhesive layer has a groove-like pattern, it exhibits appropriate wettability and can ensure more sufficient adhesive reliability. A more preferred lower limit of the content of constituent units derived from the above hydroxyl group-containing monomer is 0.05% by mass, a more preferred upper limit is 1.0% by mass, and an even more preferred lower limit is 0.1% by mass.

[0068] In the above (meth)acrylic copolymer, the preferred lower limit for the content of constituent units derived from the carboxyl group-containing monomer is 0.1% by mass, and the preferred upper limit is 15% by mass. When the content of constituent units derived from the carboxyl group-containing monomer is within the above range, the adhesive layer tends to have appropriate hardness, the groove-like pattern formed on the adhesive layer is less likely to disappear, and even when the adhesive layer has a groove-like pattern, it exhibits appropriate wettability, and the adhesive tape can ensure more sufficient adhesive reliability. A more preferred lower limit for the content of constituent units derived from the carboxyl group-containing monomer is 0.5% by mass, a more preferred upper limit is 12% by mass, an even more preferred lower limit is 1.5% by mass, and an even more preferred upper limit is 10% by mass.

[0069] The above (meth)acrylic copolymer may have constituent units derived from other monomers other than the above alkyl (meth)acrylate and the above monomer having a crosslinkable functional group, to the extent that it does not impair the effects of the present invention.

[0070] Other monomers mentioned above include, for example, benzyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and polypropylene glycol mono(meth)acrylate. Furthermore, other monomers commonly used as raw materials for (meth)acrylic copolymers, such as vinyl acetate and styrene, can also be used.

[0071] The monomer having the above-mentioned crosslinkable functional group and the other monomers preferably include bio-derived materials, but may consist solely of petroleum-derived materials. Theoretically, it is possible to use monomers that consist entirely of bio-derived materials for the acrylic copolymer described above. From the standpoint of cost and productivity of the adhesive composition, monomers containing relatively inexpensive and readily available bio-derived materials may be used, and these may be combined with monomers consisting solely of petroleum-derived materials.

[0072] The preferred lower limit of the weight-average molecular weight (Mw) of the above (meth)acrylic copolymer is 300,000, and the preferred upper limit is 1,500,000. When the weight-average molecular weight of the above (meth)acrylic copolymer is within this range, the adhesive layer tends to have appropriate hardness, the groove-like pattern formed on the adhesive layer becomes less likely to disappear, and even when the adhesive layer has a groove-like pattern, it exhibits appropriate wettability, ensuring greater adhesive reliability for the adhesive tape. A more preferred lower limit of the weight-average molecular weight of the above (meth)acrylic copolymer is 500,000, a more preferred upper limit is 1,400,000, an even more preferred lower limit is 700,000, and an even more preferred upper limit is 1,300,000.

[0073] The ratio of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) of the above (meth)acrylic copolymer (polydispersity, Mw / Mn) has a preferred upper limit of 7.0. A polydispersity of 7.0 or less for the above (meth)acrylic copolymer allows the adhesive layer to have appropriate bulk strength, thus making it easier for the adhesive layer to have appropriate hardness and making the groove-like pattern formed on the adhesive layer less likely to disappear. A more preferred upper limit for the polydispersity of the above (meth)acrylic copolymer is 5.0. Furthermore, the polydispersity of the (meth)acrylic copolymer is not particularly limited, but a preferred lower limit is 1.1. When the polydispersity of the (meth)acrylic copolymer is 1.1 or higher, the adhesive layer tends to have appropriate hardness, and even when the adhesive layer has a groove-like pattern, it exhibits appropriate wettability, and the adhesive tape can ensure more sufficient adhesive reliability. A more preferred lower limit for the polydispersity (Mw / Mn) of the (meth)acrylic copolymer is 2.0.

[0074] The above (meth)acrylic copolymer more preferably has a weight-average molecular weight of 300,000 to 1,500,000 and a polydispersity of 7.0 or less. When the weight-average molecular weight and polydispersity of the above (meth)acrylic copolymer meet this range, the adhesive layer has appropriate bulk strength, the adhesive layer tends to have appropriate hardness, the groove-like pattern formed on the adhesive layer is less likely to disappear, and even when the adhesive layer has a groove-like pattern, it exhibits appropriate wettability, and the adhesive tape can ensure more sufficient adhesive reliability.

[0075] In this specification, the weight-average molecular weight and number-average molecular weight refer to the weight-average molecular weight and number-average molecular weight on a standard polystyrene basis, measured by GPC (Gel Permeation Chromatography). Specifically, a sample is prepared by diluting a sample compound, such as a (meth)acrylic copolymer, 50-fold with an organic solvent such as tetrahydrofuran (THF), and filtering the resulting dilution through a filter (material: polytetrafluoroethylene, pore diameter: 0.2 μm). Next, this sample is supplied to a gel permeation chromatograph, and GPC measurement is performed under conditions of a sample flow rate of 1 mL / min and a column temperature of 40°C. The polystyrene-based molecular weight of the sample compound is measured, and this value is taken as the weight-average molecular weight and number-average molecular weight (Mn) of the sample compound. An example of the gel permeation chromatograph is the 2690 Separations Module (manufactured by Waters). Furthermore, the polydispersity (Mw / Mn) can be calculated using the obtained weight-average molecular weight (Mw) and number-average molecular weight (Mn).

[0076] The above (meth)acrylic copolymer can be obtained by polymerizing a mixture of constituent monomer units in the presence of a polymerization initiator through a radical reaction. Examples of the radical reaction methods mentioned above include living radical polymerization and free radical polymerization. Living radical polymerization yields copolymers with more uniform molecular weight and composition compared to free radical polymerization, and suppresses the generation of low molecular weight components. As a result, the resulting adhesive composition exhibits greater cohesive force and thus better adhesion to the adherend. Conventional known methods can be used to polymerize the above monomer mixture, including, for example, solution polymerization (boiling point polymerization or constant temperature polymerization), UV polymerization, emulsion polymerization, suspension polymerization, and bulk polymerization. Among these, solution polymerization and UV polymerization are preferred because they result in adhesive compositions that exhibit better adhesion to the substrate. When solution polymerization is used as the method for polymerizing the above monomer mixture, examples of reaction solvents include ethyl acetate, toluene, methyl ethyl ketone, dimethyl sulfoxide, ethanol, acetone, and diethyl ether.

[0077] Examples of polymerization initiators include organic peroxides and azo compounds. Examples of the above-mentioned organic peroxides include 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane, t-hexylperoxypivalate, t-butylperoxypivalate, 2,5-dimethyl-2,5-bis(2-ethylhexanoylperoxy)hexane, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyisobutyrate, t-butylperoxy-3,5,5-trimethylhexanoate, and t-butylperoxylaurate. Examples of the above-mentioned azo compounds include azobisisobutyronitrile and azobiscyclohexanecarbonitride. Furthermore, if the radical reaction method is living radical polymerization, examples of polymerization initiators include organic tellurium polymerization initiators. The organic tellurium polymerization initiator is not particularly limited as long as it is commonly used in living radical polymerization, and examples include organic tellurium compounds and organic telluride compounds. In addition, in living radical polymerization, an azo compound may be used as a polymerization initiator in addition to the organic tellurium polymerization initiator to accelerate the polymerization rate.

[0078] The preferred lower limit for the content of the (meth)acrylic copolymer in the above adhesive composition is 50% by mass, and the preferred upper limit is 90% by mass. When the content of the (meth)acrylic copolymer is within this range, the adhesive layer tends to have appropriate hardness, the groove-like pattern formed on the adhesive layer is less likely to disappear, and even when the adhesive layer has a groove-like pattern, it exhibits appropriate wettability, and the adhesive tape can ensure more sufficient adhesive reliability. The more preferred lower limit for the content of the (meth)acrylic copolymer is 55% by mass, and the more preferred upper limit is 80% by mass.

[0079] Furthermore, the above adhesive composition may contain a rubber-based resin as the base polymer. By including a rubber-based resin in the above adhesive composition, it becomes easier to design the storage modulus of the adhesive layer at 85°C to be high, the pattern of the adhesive layer is less likely to disappear with respect to the thermal history after the separator is replaced, and the air release properties of the adhesive tape with separator can be improved. Examples of the above-mentioned rubber-based resins include styrene elastomers, nitrile elastomers, hydrogenated nitrile elastomers, chloroprene elastomers, acrylic elastomers, urethane elastomers, chlorosulfonated polyethylene elastomers, fluorosilicone elastomers, butadiene elastomers, and styrene-butadiene elastomers, among which styrene elastomers are preferred.

[0080] Examples of the styrene-based elastomers include a block copolymer (A) of a monovinyl-substituted aromatic compound block and a conjugated diene compound block (hereinafter sometimes simply referred to as "block copolymer (A)"), and a hydrogenated form of the block copolymer (A). In particular, from the viewpoint of further improving the shear storage modulus of the adhesive layer at 85°C, it is preferable that the styrene-based elastomer includes a hydrogenated form of the block copolymer (A). The block copolymer (A) described above is a block copolymer having rubber elasticity at room temperature and containing a hard segment portion and a soft segment portion, wherein the monovinyl-substituted aromatic compound block is the hard segment portion and the conjugated diene compound block is the soft segment portion. Furthermore, in this specification, "hydrogenated block copolymer (A)" means a block copolymer (A) in which, of the double bonds (unsaturated bonds) of the repeating units derived from the conjugated diene compound described later, preferably 80% or more, more preferably 90% or more, even more preferably 95% or more, and even more preferably 96% or more are converted to saturated bonds by hydrogenation. Also, the hydrogenation ratio (hydrogenation rate) of the above block (A) copolymer may be 100%, that is, the hydrogenated block (A) copolymer may be a partially hydrogenated or fully hydrogenated product. The above hydrogenation rate is measured using deuterated chloroform as a solvent at 20 Hz. 1 This can be calculated by measuring the H-NMR spectrum.

[0081] Examples of the monovinyl-substituted aromatic compounds include styrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, α-methylstyrene, 2,4-dimethylstyrene, 2,4-diisopropylstyrene, 4-t-butylstyrene, 5-t-butyl-2-methylstyrene, vinylethylbenzene, divinylbenzene, trivinylbenzene, divinylnaphthalene, t-butoxystyrene, vinylbenzyldimethylamine, (4-vinylbenzyl)dimethylaminoethyl ether, N,N-dimethylaminoethylstyrene, N,N-dimethylaminomethylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2-t-butylstyrene, 3-t-butylstyrene, 4-t-butylstyrene, vinylxylene, vinylnaphthalene, vinylpyridine, diphenylethylene, and tertiary amino group-containing diphenylethylene. Examples of the tertiary amino group-containing diphenylethylene include 1-(4-N,N-dimethylaminophenyl)-1-phenylethylene. Among these, styrene is preferred because it is readily available industrially. These monovinyl-substituted aromatic compounds may be used individually or in combination of two or more.

[0082] Examples of the above-mentioned conjugated diene compounds include isoprene, 1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 1,3-heptadiene, 2-phenyl-1,3-butadiene, 3-methyl-1,3-pentadiene, and 2-chloro-1,3-butadiene. Among these, isoprene and butadiene are preferred, with isoprene being more preferred, from the viewpoint of balancing slurry properties and adhesion to rough surfaces. These conjugated diene compounds may be used individually or in combination of two or more.

[0083] Examples of the block copolymer (A) mentioned above include styrene-isoprene-styrene (SIS) block copolymer, styrene-butadiene-styrene (SBS) block copolymer, and styrene-butadiene-butylene-styrene (SBBS) block copolymer. Examples of hydrogenated materials for the block copolymer (A) include styrene-ethylene-butylene-styrene (SEBS) block copolymer, styrene-ethylene-propylene-styrene (SEPS) block copolymer, and hydrogenated styrene-butylene rubber (HSBR). Among these, it is preferable to include styrene-isoprene-styrene (SIS) block copolymer because it has sufficient flexibility to exhibit good adhesion to rough surfaces. These block copolymers may be used individually or in combination of two or more types.

[0084] The block copolymer (A) preferably includes a triblock copolymer of the hard segment portion and the soft segment portion, and may also include a diblock copolymer of the hard segment portion and the soft segment portion in addition to the triblock copolymer.

[0085] The block copolymer (A) above preferably contains a block copolymer having a styrene content of 10% to 20% by mass and a diblock content of 25% to 80% by mass. In this case, the shear storage modulus of the adhesive layer at 85°C is further improved. The block copolymer (A) above more preferably contains a block copolymer having a styrene content of 10% to 20% by mass and a diblock content of 50% to 80% by mass. In particular, the block copolymer (A) above more preferably contains only a block copolymer having a styrene content of 10% to 20% by mass and a diblock content of 50% to 80% by mass. In this specification, "styrene content" refers to the content of the hard segment portion when the monovinyl-substituted aromatic compound in the block copolymer (A) is styrene, and "hard segment content" refers to the content of the monovinyl-substituted aromatic compound.

[0086] The preferred lower limit for the weight-average molecular weight of the block copolymer (A) is 20,000, and the preferred upper limit is 600,000. If the weight-average molecular weight of the block copolymer (A) is 20,000 or more, the shear storage modulus of the adhesive layer at 85°C is further improved. If the weight-average molecular weight of the block copolymer (A) is 600,000 or less, the compatibility between the block copolymer (A) and other components is further improved. The more preferred lower limit for the weight-average molecular weight of the block copolymer (A) is 50,000, and the more preferred upper limit is 500,000.

[0087] From the viewpoint of being able to appropriately adjust the degree of crosslinking, it is preferable that the above adhesive composition further contains a crosslinking agent.

[0088] In the above adhesive composition, the preferred lower limit of the crosslinking agent content per 100 parts by mass of the base polymer is 0.01 parts by mass, and the preferred upper limit is 10 parts by mass. When the crosslinking agent content is within this range, the adhesive layer is more likely to form a crosslinked structure, making the adhesive layer more rigid, and thus the groove-like pattern formed on the adhesive layer is less likely to disappear. As a result, the adhesive tape with separator exhibits superior air release properties when the adhesive tapes are bonded together. A more preferred lower limit for the crosslinking agent content is 0.1 parts by mass, a more preferred upper limit is 7.0 parts by mass, an even more preferred lower limit is 0.2 parts by mass, and an even more preferred upper limit is 5.0 parts by mass. In this specification, the term "content of the crosslinking agent" refers to the content of the solids of the crosslinking agent.

[0089] Examples of the above-mentioned crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, aziridine-based crosslinking agents, and metal chelate-based crosslinking agents. In particular, it is preferable that the above-mentioned crosslinking agent includes at least one selected from the group consisting of isocyanate-based crosslinking agents and epoxy-based crosslinking agents. By including at least one selected from the group consisting of isocyanate-based crosslinking agents and epoxy-based crosslinking agents, it becomes easier to adjust the degree of crosslinking of the adhesive layer and to make the adhesive layer appropriately hard. As a result, the groove-like pattern formed on the adhesive layer is less likely to disappear, and even when the adhesive layer has a groove-like pattern, it exhibits appropriate wettability, and the adhesive tape can ensure more sufficient adhesive reliability. The above crosslinking agent may be of one type, or two or more types may be used in combination.

[0090] The above adhesive composition may further contain a crosslinking catalyst to promote crosslinking by the above crosslinking agent. Examples of the crosslinking catalysts mentioned above include dibutyltin dilaurate, dibutyltin diacetate, and dioctyltin dilaurate, which are used as crosslinking catalysts for the isocyanate-based crosslinking agents.

[0091] Preferably, the above adhesive composition further contains a tackifying resin. By including a tackifying resin in the adhesive composition, the adhesive layer has better adhesive strength, and the resulting adhesive tape can be more effectively prevented from peeling off. In addition, the adhesive layer becomes harder, making it less likely for the groove-like pattern formed on the adhesive layer to disappear. As a result, the adhesive tape with separator has better air release properties when the adhesive tapes are bonded together.

[0092] In the above adhesive composition, the preferred lower limit of the content of the tackifying resin per 100 parts by mass of the base polymer is 10 parts by mass, and the preferred upper limit is 50 parts by mass. When the content of the tackifying resin is 10 parts by mass or more, the adhesive strength of the adhesive layer is further improved, and the adhesive layer becomes harder. When the content of the tackifying resin is 50 parts by mass or less, the adhesive layer does not become too hard, and even when the adhesive layer has a groove-like pattern, it exhibits appropriate wettability, and the adhesive tape can ensure more sufficient adhesive reliability. A more preferred lower limit of the content of the tackifying resin is 20 parts by mass, a more preferred upper limit is 45 parts by mass, an even more preferred lower limit is 30 parts by mass, and an even more preferred upper limit is 40 parts by mass.

[0093] The tackifying resins mentioned above are not particularly limited and include, for example, rosin ester tackifying resins, terpene tackifying resins, coumarone indene tackifying resins, aliphatic hydrocarbon tackifying resins, C5 petroleum tackifying resins, C9 petroleum tackifying resins, and C5-C9 copolymer petroleum tackifying resins. Among these, at least one selected from the group consisting of rosin ester tackifying resins and terpene tackifying resins is preferred. These tackifying resins may be used individually or in combination of two or more types.

[0094] Examples of the rosin ester-based tackifying resins mentioned above include polymerized rosin ester resins and hydrogenated rosin ester resins. Examples of the terpene-based tackifying resins mentioned above include terpene resins and terpene phenol resins.

[0095] Examples of the above-mentioned rosin ester resins include Pencel D-135, Pine Crystal KE-359, Ester Gum AA-V, Ester Gum H, Super Ester A-115, Super Ester A-125 (all manufactured by Arakawa Chemical Industries, Ltd.), and Haritack PCJ (manufactured by Harima Chemicals Co., Ltd.). Examples of the terpene-based resins mentioned above include YS Resin PX1250, YS Resin PX1150, YS Polystar G150, and YS Polystar T130 (all manufactured by Yasuhara Chemical Co., Ltd.). Examples of the above-mentioned coumaron-indene-based tackifying resins include, for example, Nitresin Coumaron V-120 (manufactured by Nippon Paint Chemical Co., Ltd.). Examples of the above-mentioned aliphatic hydrocarbons include Quintone M-100 (manufactured by Zeon Corporation).

[0096] The tackifying resin described above is preferably of biological origin. The fact that the tackifying resin is of biological origin makes it easier to increase the content of biologically derived carbon in the adhesive layer described later. Examples of the above-mentioned bio-derived tackifying resins include bio-derived rosin ester-based tackifying resins and bio-derived terpene-based tackifying resins. Examples of the above-mentioned biologically derived rosin ester tackifying resins include, for instance, rosin ester tackifying resins derived from natural resins such as pine resin. Examples of the above-mentioned biologically derived terpene-based tackifying resins include, for instance, terpene-based tackifying resins derived from plant essential oils, etc.

[0097] The tackifying resin preferably includes a tackifying resin having a softening point of 80°C to 170°C. By including a tackifying resin having a softening point of 80°C to 170°C, the shear storage modulus of the adhesive layer at 23°C, as measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz described later, can be easily adjusted to 0.1 MPa or higher. A more preferable lower limit for the softening point of the tackifying resin is 90°C, a more preferable upper limit is 160°C, an even more preferable lower limit is 100°C, and an even more preferable upper limit is 150°C. In this specification, the term "softening point" refers to the softening point measured by a method conforming to JIS K 2207 (ring-sphere method).

[0098] The above tackifying resin preferably includes a tackifying resin having a hydroxyl value of 20 mg KOH / g or more and 150 mg KOH / g or less. Including a tackifying resin with a hydroxyl value of 20 mg KOH / g or more and 150 mg KOH / g or less makes it easier to adjust the degree of crosslinking of the adhesive layer, thus making it easier to adjust the hardness of the adhesive layer. A more preferred lower limit for the hydroxyl value of the above tackifying resin is 30 mg KOH / g, a more preferred upper limit is 140 mg KOH / g, an even more preferred lower limit is 40 mg KOH / g, and an even more preferred upper limit is 130 mg KOH / g. The hydroxyl value can be measured according to JIS K1557 (phthalic anhydride method).

[0099] The above adhesive composition may further contain a pigment. By including a pigment in the above adhesive composition, the resulting adhesive tape can be given light-shielding properties.

[0100] The above-mentioned pigments are not particularly limited as long as they are coloring agents, but from the viewpoint of further improving the light-shielding properties of the resulting adhesive tape, pigments that color the tape black or gray are preferred, and specifically, black fillers are preferred. Examples of the black fillers mentioned above include carbon black and titanium black.

[0101] The average particle size of the black filler described above has a preferred lower limit of 0.01 μm and a preferred upper limit of 1.0 μm. Having the average particle size of the black filler within this range allows the resulting adhesive tape to exhibit better light-shielding properties. A more preferred lower limit for the average particle size of the black filler is 0.1 μm, and a more preferred upper limit is 0.8 μm. The average particle size can be determined, for example, by observing 50 arbitrary inorganic fillers with an electron microscope or optical microscope and calculating the average particle size of each inorganic filler, or by performing laser diffraction particle size distribution measurement.

[0102] The above adhesive composition may optionally contain additives such as silane coupling agents, plasticizers, softeners, and fillers, as long as they do not impair the effects of the present invention.

[0103] The adhesive layer described above has a preferred lower limit of 0.1 MPa for the shear storage modulus at 23°C, as measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz (hereinafter sometimes simply referred to as "the shear storage modulus of the adhesive layer at 23°C"). A shear storage modulus of 0.1 MPa or higher for the adhesive layer makes it easier for the adhesive layer to become harder and prevents the groove-like pattern formed on the adhesive layer from disappearing. Therefore, the adhesive tape with separator exhibits superior air release properties when the adhesive tapes are bonded together. A more preferred lower limit for the shear storage modulus of the adhesive layer at 23°C is 0.2 MPa, and an even more preferred lower limit is 0.3 MPa. Furthermore, a preferred upper limit for the shear storage modulus of the adhesive layer at 23°C is 10 MPa. Having a shear storage modulus of 10 MPa or less at 23°C prevents the adhesive layer from becoming too hard and maintains appropriate wettability. Even if the adhesive layer has a grooved pattern, the adhesive tape can ensure greater adhesive reliability. A more preferred upper limit for the shear storage modulus of the adhesive layer at 23°C is 5 MPa, and an even more preferred upper limit is 3 MPa.

[0104] The adhesive layer described above has a preferred lower limit of 0.02 MPa for the shear storage modulus at 85°C, as measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz (hereinafter sometimes simply referred to as "the shear storage modulus of the adhesive layer at 85°C"). A shear storage modulus of 0.02 MPa or higher for the adhesive layer makes the groove-like pattern formed on the surface less likely to disappear even in high-temperature environments, thus providing superior air release properties when bonding adhesive tapes, even in high-temperature environments. A more preferred lower limit for the shear storage modulus of the adhesive layer at 85°C is 0.03 MPa, and an even more preferred lower limit is 0.04 MPa. Furthermore, a preferred upper limit for the shear storage modulus of the adhesive layer at 85°C is 1.0 MPa. A shear storage modulus of 1.0 MPa or less at 85°C ensures that the adhesive layer does not become excessively hard and maintains appropriate wettability even in high-temperature environments. This allows the adhesive tape to maintain sufficient adhesive reliability even in high-temperature environments, even if the adhesive layer has a grooved pattern. A more preferred upper limit for the shear storage modulus of the adhesive layer at 85°C is 0.6 MPa, and an even more preferred upper limit is 0.4 MPa.

[0105] The shear storage modulus of the adhesive layer at 23°C and the shear storage modulus of the adhesive layer at 85°C are measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz. Specifically, the adhesive layer of the separator-attached adhesive tape is first removed by scraping it off with a utility knife, and the removed adhesive layers are stacked to create a laminate consisting only of adhesive layers with a thickness of approximately 1 mm. This laminate is then cut to a width of 6 mm and a length of 10 mm to obtain a test specimen. The obtained test specimen is then subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (IT Measurement Control Co., Ltd., "DVA-200") in shear mode, under nitrogen atmosphere conditions, with a measurement temperature range of -40°C to 200°C, a heating rate of 5°C / min, a frequency of 10 Hz, and a strain of 0.08%. Alternatively, a test specimen may be prepared using a sheet approximately 1 mm thick consisting solely of the adhesive layer described above, and dynamic viscoelasticity measurements may be performed.

[0106] Methods for adjusting the shear storage modulus of the adhesive layer at 23°C and the shear storage modulus of the adhesive layer at 85°C include, for example, adjusting the type and content ratio of the constituent unit monomers of the (meth)acrylic copolymer (for example, using the (meth)alkyl acrylates (a) to (e) above as the (meth)alkyl acrylate and adjusting their type and content ratio), adjusting the type and content of the tackifying resin contained in the adhesive composition (for example, adjusting the softening point and hydroxyl value of the tackifying resin), and adjusting the type and content of the crosslinking agent. Another method involves using a rubber-based resin as the base polymer and adjusting the type of constituent units of the hard segment portion and the soft segment portion of the rubber-based resin, the weight-average molecular weight of the rubber-based resin, and the content of the rubber-based resin.

[0107] The adhesive layer described above has a preferred lower limit of 0°C for its glass transition temperature (hereinafter sometimes simply referred to as "glass transition temperature of the adhesive layer"), which is measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz. A glass transition temperature of 0°C or higher for the adhesive layer makes it easier for the adhesive layer to become harder and prevents the groove-like pattern formed on the adhesive layer from disappearing. Therefore, the adhesive tape with separator exhibits superior air release properties when the tapes are bonded together. A more preferred lower limit for the glass transition temperature of the adhesive layer is 5°C, and an even more preferred lower limit is 10°C. Furthermore, a preferred upper limit for the glass transition temperature of the adhesive layer is 35°C. A glass transition temperature of 35°C or lower prevents the adhesive layer from becoming too hard and maintains appropriate wettability. Even if the adhesive layer has a grooved pattern, the adhesive tape can ensure greater adhesive reliability. A more preferred upper limit for the glass transition temperature of the adhesive layer is 30°C, and an even more preferred upper limit is 25°C. In this specification, the "glass transition temperature of the adhesive layer" refers to the temperature at which a maximum of loss tangent (tanδ) obtained by dynamic viscoelasticity measurement occurs, which is attributed to micro-Brownian motion.

[0108] The glass transition temperature of the adhesive layer described above is measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz. Specifically, first, the adhesive layer of the separator-attached adhesive tape is removed by scraping it off with a utility knife, and the removed adhesive layers are stacked to create a laminate consisting only of adhesive layers with a thickness of approximately 1 mm. This laminate is then cut to a width of 6 mm and a length of 10 mm to obtain a test specimen. Then, dynamic viscoelasticity measurements are performed on the obtained test specimen using a dynamic viscoelasticity measuring device (IT Measurement Control Co., Ltd., "DVA-200") in shear mode under nitrogen atmosphere conditions, with a measurement temperature range of -40°C to 200°C, a heating rate of 5°C / min, a frequency of 10 Hz, and a strain of 0.08%. After this, the glass transition temperature of the adhesive layer can be obtained by reading the resulting dynamic viscoelasticity spectrum. Alternatively, a test specimen may be prepared using a sheet approximately 1 mm thick consisting solely of the adhesive layer described above, and dynamic viscoelasticity measurements may be performed.

[0109] Methods for adjusting the glass transition temperature of the adhesive layer include, for example, adjusting the type and content ratio of the constituent unit monomers of the (meth)acrylic copolymer (for example, using the (meth)alkyl acrylates (a) to (e) above as the (meth)alkyl acrylate and adjusting their type and content ratio), adjusting the type and content of the tackifying resin contained in the adhesive composition (for example, adjusting the softening point and hydroxyl value of the tackifying resin), and adjusting the type and content of the crosslinking agent. Another method involves using a rubber-based resin as the base polymer and adjusting the type of constituent units of the hard segment portion and the soft segment portion of the rubber-based resin, the weight-average molecular weight of the rubber-based resin, and the content of the rubber-based resin.

[0110] A preferred lower limit for the gel fraction of the adhesive layer is 20% by mass. When the gel fraction of the adhesive layer is 20% by mass or more, the adhesive layer tends to become harder, and the groove-like pattern formed on the adhesive layer becomes less likely to disappear, so the resulting adhesive tape with separator has better air release properties when the adhesive tapes are bonded together. A more preferred lower limit for the gel fraction of the adhesive layer is 25% by mass, and an even more preferred lower limit is 30% by mass. Furthermore, the preferred upper limit for the gel fraction of the adhesive layer is 70% by mass. A gel fraction of 70% by mass or less in the adhesive layer prevents it from becoming too hard and maintains appropriate wettability. Even when the adhesive layer has a grooved pattern, the adhesive tape can ensure greater adhesive reliability. Additionally, the resulting adhesive tape will have superior handling properties. A more preferred upper limit for the gel fraction of the adhesive layer is 60% by mass, and an even more preferred upper limit is 50% by mass.

[0111] The gel fraction of the adhesive layer described above is measured by the following methods, etc. Specifically, first, a test specimen is prepared by cutting the adhesive tape having the adhesive layer described above into a flat rectangular shape with a width of 20 mm and a length of 40 mm. The test specimen is then immersed in ethyl acetate at 23°C for 24 hours, removed from the ethyl acetate, and dried at 110°C for 1 hour. The mass of the dried test specimen is measured, and the gel fraction is calculated using the following formula (i). Note that no separator is laminated on the test specimen. If the adhesive tape is a non-support type tape without a base material, the measurement is performed using a test specimen obtained by attaching it to a base material and then cutting it, or the calculation is performed by setting W0 in the following formula (i) to 0 without using a base material. Gel fraction (mass %) = 100 × (W2 - W0) / (W1 - W0) (i) (W0: Mass of the substrate, W1: Mass of the test specimen before immersion, W2: Mass of the test specimen after immersion and drying)

[0112] Methods for adjusting the gel fraction of the adhesive layer include, for example, adjusting the type and content ratio of the constituent unit monomers of the (meth)acrylic copolymer (for example, using the above-mentioned (meth)alkyl acrylates (a) to (e) as the (meth)alkyl acrylate and adjusting their type and content ratio), adjusting the type and content of the tackifying resin contained in the adhesive composition (for example, adjusting the softening point and hydroxyl value of the tackifying resin), and adjusting the type and content of the crosslinking agent.

[0113] The preferred lower limit for the bio-derived carbon content in the adhesive layer is 10%. A separator-attached adhesive tape with a bio-derived carbon content of 10% or more in the adhesive layer is superior in terms of conserving petroleum resources and reducing carbon dioxide emissions, thus reducing environmental impact. A more preferred lower limit for the bio-derived carbon content in the adhesive layer is 40%, and an even more preferred lower limit is 60%. Furthermore, there is no particular upper limit to the content of bio-derived carbon in the adhesive layer described above, and it may be 100%. Furthermore, while bio-derived carbon contains a certain percentage of the radioactive isotope (C-14), petroleum-derived carbon contains almost no C-14. Therefore, the "biologically derived carbon content" as used herein can be calculated by measuring the concentration of C-14 contained in the adhesive layer. Specifically, it can be measured in accordance with ASTM D6866-24, a standard widely used in the bioplastics industry.

[0114] The thickness of the adhesive layer described above has a preferred upper limit of 120 μm. A thickness of 120 μm or less of the adhesive layer allows the resulting separator-equipped adhesive tape to be more suitably used for fixing components in thin electronic devices. A more preferred upper limit for the thickness of the adhesive layer is 80 μm, and an even more preferred upper limit is 65 μm. Furthermore, the lower limit of the thickness of the adhesive layer is not particularly limited and can be greater than 0 μm, but from the viewpoint of ensuring adhesive reliability while fixing the components, a preferred lower limit is 5 μm.

[0115] The types of substrates mentioned above are not particularly limited and include, for example, films, nonwoven fabrics, foamed sheets, metals, and glass. Among these, films and foamed sheets are preferred from the viewpoint of ease of availability, variety, and ease of processing.

[0116] The above-mentioned films are not particularly limited and include, for example, polyester films such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polyolefin films such as polyethylene (PE), polyimide (PI) films, and polycarbonate (PCC) films. The nonwoven fabrics mentioned above are not particularly limited and include, for example, polyester-based synthetic fibers and polypropylene-based synthetic fibers. The foamed sheets mentioned above are not particularly limited and include, for example, polyurethane foamed sheets, polyolefin foamed sheets such as polyolefin and polypropylene, styrene-acrylic foamed sheets, and acrylic-olefin foamed sheets. Examples of the above-mentioned metals include copper plates and aluminum plates. Examples of the above-mentioned glass include ultra-thin glass (UTG).

[0117] From the viewpoint of increasing the content of bio-derived carbon in the adhesive tape as a whole, a substrate made of bio-derived material is preferred. Examples of the above-mentioned bio-derived materials include polyesters (PES) such as polyethylene terephthalate (PET), polyethylene furanoate (PEF), polylactic acid (PLA), polytrimethylene terephthalate (PTT), polybutylene terephthalate (PBT), and polybutylene succinate (PBS), as well as polyethylene (PE), polypropylene (PP), polyurethane (PU), triacetylcellulose (TAC), cellulose, and polyamide (PA), all of which are derived from plants.

[0118] Furthermore, from the perspective of reducing environmental impact by decreasing the use of new petroleum resources and suppressing carbon dioxide emissions, it is also preferable to use base materials made from recycled resources. Methods for recycling resources include, for example, recovering waste from packaging containers, home appliances, automobiles, construction materials, food, etc., or waste generated in the manufacturing process, and using the extracted materials again as raw materials by washing, decontamination, or decomposition by heating or fermentation. Examples of base materials using the above recycled resources include films and nonwoven fabrics made from PET, PBT, PE, PP, PA, etc., using recovered plastics that have been re-resinated as raw materials. Alternatively, the recovered waste may be burned and used as thermal energy for the manufacture of base materials and their raw materials, or the oils and fats contained in the recovered waste may be mixed with petroleum, fractionated, and refined to be used as raw materials.

[0119] The above-mentioned substrate may be a colored substrate. When the above-mentioned substrate is colored, the resulting adhesive tape can be given excellent light-shielding properties. Therefore, the resulting adhesive tape can be suitably used for fixing electronic equipment components or automotive components.

[0120] The color used to color the above-mentioned substrate is not particularly limited, but from the viewpoint of further improving the light-shielding properties of the resulting adhesive tape, it is preferable that the substrate is colored black or gray.

[0121] Examples of the colored substrates mentioned above include substrates made from materials containing colorants such as pigments as components of the substrate material, and substrates in which a colored layer is coated on the surface of the substrate material.

[0122] Examples of pigments in the materials constituting the above-mentioned substrate include those similar to those in the adhesive composition described above.

[0123] Examples of substrates coated with a colored layer on the surface include, for example, a substrate coated with a coloring agent such as the aforementioned pigment on its surface, or a substrate with a color print on its surface.

[0124] When the above-mentioned substrate is a substrate on which a colored layer is coated on the surface of the substrate, the preferred lower limit of the ratio of the thickness of the colored layer to the thickness of the substrate is 1%, and the preferred upper limit is 50%. When the ratio of the thickness of the colored layer is 1% or more, the resulting adhesive tape can be given superior light-shielding properties. When the ratio of the thickness of the colored layer is 50% or less, the rigidity of the substrate tends to be within an appropriate range, and the handling properties of the adhesive tape are further improved. A more preferred lower limit of the ratio of the thickness of the colored layer is 5%, a more preferred upper limit is 40%, an even more preferred lower limit is 10%, and an even more preferred upper limit is 35%. Furthermore, the proportion of the colored layer varies depending on the thickness of the target substrate layer, so the above proportion of the colored layer thickness is not necessarily limited to this.

[0125] The preferred lower limit for the thickness of the above substrate is 3 μm, and the preferred upper limit is 2000 μm. When the thickness of the above substrate is within this range, the rigidity of the substrate tends to be within an appropriate range, the handling properties of the above adhesive tape are further improved, and the above adhesive tape can further suppress air incorporation when it is applied to the adherend. A more preferred lower limit for the thickness of the above substrate is 5 μm, a more preferred upper limit is 1500 μm, an even more preferred lower limit is 10 μm, an even more preferred upper limit is 1000 μm, an even more preferred lower limit is 15 μm, and an even more preferred upper limit is 300 μm.

[0126] The above adhesive tape has a preferred lower limit of 5 μm and a preferred upper limit of 2500 μm in total thickness. Having the total thickness of the above adhesive tape within this range improves the selectivity of the members and parts to be fixed, allowing for more suitable use in fixing members and parts in articles for various applications. A more preferred lower limit of the total thickness of the above adhesive tape is 10 μm, a more preferred upper limit is 2000 μm, an even more preferred lower limit is 20 μm, and an even more preferred upper limit is 1000 μm.

[0127] The above-mentioned adhesive tape with separator has a separator. Examples of separator substrates in the above-mentioned separator include paper, nonwoven fabric, and film. In particular, from the viewpoint of ensuring strength that prevents breakage when replacing the separator, it is preferable that the above-mentioned separator includes at least one selected from the group consisting of paper and film as the separator substrate.

[0128] Examples of the above-mentioned papers include high-quality paper and kraft paper. Examples of the above-mentioned films include polyester films such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polypropylene films, and polycarbonate films. Among these, PET film is preferred from the standpoint of ease of availability and wide variety of types.

[0129] In the adhesive tape with separator according to the present invention 3, the separator has a ridged pattern. Because the separator has a ridged pattern, the ridged pattern is transferred to the adhesive layer adjacent to the separator, thereby forming a groove-like pattern in the adhesive layer that fits into the ridged pattern, and the resulting adhesive tape with separator has excellent air release properties when adhesive tapes are bonded together. Furthermore, in the adhesive tapes with separators according to inventions 1 and 2, it is preferable that the separator has a ridged pattern. By having a ridged pattern on the separator, the ridged pattern is transferred to the adhesive layer adjacent to the separator, so that the adhesive layer has a grooved pattern that fits into the ridged pattern, and the resulting adhesive tape with separator has superior air release properties when adhesive tapes are bonded together.

[0130] The shape of the protrusions in the ridged pattern of the separator described above is not particularly limited, but examples include trapezoidal, semicircular, rectangular, etc., when viewed in cross-section.

[0131] Examples of separators having the above-mentioned ridged pattern include separators having a release layer with a ridged pattern directly on the separator substrate, and separators having a resin layer with a ridged pattern on the separator substrate. Among these, separators having a resin layer with a ridged pattern on the separator substrate are preferred from the viewpoint of further improving the peeling stability of the release layer. Furthermore, a separator having a resin layer with a ridged pattern on the above-mentioned separator substrate may also have a release layer with a ridged pattern on top of the resin layer.

[0132] The above-mentioned resin layer is not particularly limited, but examples include a layer containing polyethylene, a layer containing polypropylene, etc. Among these, a layer containing polyethylene is preferred from the viewpoint of heat resistance and dimensional stability.

[0133] Silicone materials are mainly used as the release layer mentioned above. Silicone materials can be classified into emulsion type, oil type, solution type, baked type, spray type, etc. Among these, solution type silicone materials are preferred from the viewpoint of heat resistance and long-term stability of release force.

[0134] Furthermore, when laminating the layer having the above pattern onto the separator substrate, an adhesive may be used. From the viewpoint of further reducing the environmental burden of adhesive tape, it is preferable that the separator having the above-mentioned ridged pattern is a separator that uses an adhesive that does not contain toluene (a non-toluene type separator).

[0135] Examples of separators having a resin layer with a ridged pattern on the above-mentioned separator substrate include, for example, paper embossed separators (Lintec Corporation, "K11 Shiro PL(31)R-284"). Examples of separators having a release layer with a ridged pattern directly on the above-mentioned separator substrate include, for example, PET embossed separators (manufactured by Toyo Cloth Co., Ltd., "E7002-No.82").

[0136] The separator substrate described above may have irregularities on the side that does not have a ridged pattern.

[0137] The preferred lower limit for the thickness of the separator is 10 μm, and the preferred upper limit is 300 μm. A separator thickness of 10 μm or more makes it easier to set the height of the protrusions in the ridged pattern within a suitable range, further improving air release and providing superior handling during processing. A separator thickness of 300 μm or less ensures that the weight of the adhesive tape with separator does not become too large when handled in a roll, thus ensuring good handling. A more preferred lower limit for the thickness of the separator is 23 μm, a more preferred upper limit is 250 μm, an even more preferred lower limit is 35 μm, and an even more preferred upper limit is 210 μm.

[0138] When the above-mentioned adhesive tape with separators has separators on both sides, it is preferable that the peeling force when one separator is peeled 180° from the adhesive tape is different from the peeling force when the other separator is peeled 180° from the adhesive tape. By having different peeling forces for the separators in the above-mentioned adhesive tape with separators, when using the above-mentioned adhesive tape with separators, it is possible to prevent the separator on the adhesive layer side that is not used from peeling off when peeling off the separator on the adhesive layer side that is to be adhered to the substrate, thereby further improving the handling properties of the above-mentioned adhesive tape with separators.

[0139] The peeling force obtained by peeling the above separator from the above adhesive tape at a 180° angle can be measured by the following method, etc. Specifically, first, the adhesive tape with separator is cut to a size of 50 mm in width and 100 mm in length. Then, the separator is peeled off from one side (the side not to be measured), and a 50 μm thick PET film (such as Toyobo's "E5200#50") is backed onto the exposed adhesive layer by rolling a 2 kg rubber roller back and forth once at a speed of 20 mm / s to prepare a test specimen. Then, the prepared test specimen is subjected to a peel test in accordance with JIS Z 0237:2009, using a tensile testing machine (such as Shimadzu Corporation's "Autograph AGS-X"), at 23°C and a peeling speed of 300 mm / min, in which the separator is peeled off from the adhesive tape in a 180° direction.

[0140] One method for ensuring that the peeling forces of the separators placed on both sides of the above-mentioned adhesive tape are different when peeled 180° from the adhesive tape is to use separators on both sides that have different materials and thicknesses for the separator base material.

[0141] The method for manufacturing the above-mentioned adhesive tape with separator is not particularly limited and can be manufactured by conventionally known manufacturing methods. For example, in the case of the above-mentioned adhesive tape with separator having a base material, the following methods can be used. Specifically, first, an adhesive composition is prepared by the method described above. The obtained adhesive composition is applied to the surface of the separator having a ridged pattern, and the solvent in the adhesive composition is completely dried and removed by heating to form an adhesive layer. Another adhesive layer is formed by the same method. Then, one adhesive layer is superimposed on one surface of the substrate, and the other adhesive layer is superimposed on the other surface of the substrate. After pressing and laminating the layers together with a rubber roller or the like, an adhesive tape with a separator is obtained in which adhesive layers are present on both sides of the substrate, and the surface of the adhesive layer is covered with a separator.

[0142] The applications of the above-described adhesive tape with separator are not particularly limited, but because it offers excellent air release when adhesive tapes are bonded together, it is preferably used to fix thin components that require high thickness accuracy, and more preferably to fix components of thin electronic devices. Specifically, for example, the above-described adhesive tape with separator can be suitably used to fix components of high-speed computing devices (DSPs). [Effects of the Invention]

[0143] According to the present invention, it is possible to provide an adhesive tape with a separator that offers excellent air release when adhesive tapes are bonded together. [Modes for carrying out the invention]

[0144] The embodiments of the present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The materials used in the examples and comparative examples are as follows:

[0145] <n-heptyl acrylate containing bio-derived carbon> Ricinoleic acid derived from castor oil was cracked to obtain a mixture containing undecylenic acid and n-heptyl alcohol. Then, undecylenic acid was separated from the resulting mixture by distillation to obtain n-heptyl alcohol containing bio-derived carbon. By esterifying the obtained n-heptyl alcohol containing bio-derived carbon with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), n-heptyl acrylate containing bio-derived carbon was prepared.

[0146] <1-methylheptyl acrylate containing bio-derived carbon> Ricinoleic acid derived from castor oil was dissolved in alkali to obtain a mixture containing sepacic acid and 1-methylheptyl alcohol. Next, sepacic acid was separated from the mixture by distillation to obtain 1-methylheptyl alcohol containing bio-derived carbon. The obtained 1-methylheptyl alcohol containing bio-derived carbon was esterified with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.) to prepare 1-methylheptyl acrylate containing bio-derived carbon.

[0147] <2-hydroxyethyl acrylate containing bio-derived carbon> Ethanol containing bio-derived carbon was obtained by fermenting sugars contained in sugarcane. The obtained bio-derived carbon-containing ethanol was dehydrated to obtain ethylene, and by adding water to the ethylene oxide obtained by oxidation of this ethylene glycol, bio-derived carbon was obtained. By esterifying the obtained bio-derived carbon-containing ethylene glycol with acrylic acid (manufactured by Nippon Shokubai Co., Ltd.), bio-derived carbon-containing 2-hydroxyethyl acrylate was prepared.

[0148] <Biologically derived, carbon-free monomers> • Ethyl acrylate (manufactured by Nippon Shokubai Co., Ltd.) n-butyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) • 2-Ethylhexyl acrylate (manufactured by Nippon Shokubai Co., Ltd.) • Acrylic acid (manufactured by Nippon Shokubai Co., Ltd.)

[0149] <Rubber-based resin> • SIS copolymer A: Quintac 3450 (manufactured by Zeon Corporation, styrene content: 19% by mass, diblock content: 30% by mass) • SIS copolymer B: Quintac 3433N (manufactured by Zeon Corporation, styrene content: 16% by mass, diblock content: 56% by mass)

[0150] <Adhesive-granting resin> • Tackifying resin A: Rosin ester-based tackifying resin (manufactured by Arakawa Chemical Industries, Ltd., "Pencel D-135", softening point: 140℃, hydroxyl value: 45 mgKOH / g) • Tackifying resin B: Rosin ester-based tackifying resin (Arakawa Chemical Industries, Ltd., "Pine Crystal KE-359", softening point: 100℃, hydroxyl value: 40 mgKOH / g) • Tackifying resin C: Terpene-based tackifying resin (terpene phenol-based resin) (Yasuhara Chemical Co., Ltd., "YS Polystar G150", softening point: 150℃, hydroxyl value: 130 mgKOH / g) • Tackifying resin D: Rosin ester-based tackifying resin (polymerized rosin ester resin) (manufactured by Harima Chemicals, "Haritack PCJ", softening point: 123℃) • Tackifying resin E: Rosin ester-based tackifying resin (hydrogenated rosin ester resin) (manufactured by Arakawa Chemical Industries, Ltd., "Ester Gum H", softening point: 70°C) • Tackifying resin F: Terpene-based tackifying resin (terpene phenol-based resin) (Yasuhara Chemical Co., Ltd., "YS Polystar T130", softening point: 130℃, hydroxyl value: 60mgKOH / g) • Tackifying resin G: Rosin ester-based tackifying resin (manufactured by Arakawa Chemical Industries, Ltd., "Super Ester A-115", softening point: 115℃, hydroxyl value: 25 mgKOH / g) • Tackifying resin H: Rosin ester-based tackifying resin (manufactured by Arakawa Chemical Industries, Ltd., "Super Ester A-125", softening point: 125℃, hydroxyl value: 25mgKOH / g) • Tackifying resin I: Terpene-based tackifying resin (Yasuhara Chemical Co., Ltd., "YS Resin PX1150", hydroxyl value: 0 mg KOH / g, softening point: 115℃) • Tackifying resin J: Aliphatic hydrocarbon tackifying resin (manufactured by Zeon Corporation, "Quintone M-100", hydroxyl value: 0 mg KOH / g, softening point: 100℃) • Tackifying resin K: Terpene-based tackifying resin (terpene phenol-based resin) (Yasuhara Chemical Co., Ltd., "YS Polystar T-160", hydroxyl value: 60 mg KOH / g, softening point: 160℃) • Tackifying resin L: Coumaron indene-based tackifying resin (manufactured by Nippon Paint Chemical Co., Ltd., "Nitresin Coumaron V-120", hydroxyl value: 30 mg KOH / g, softening point: 120℃)

[0151] <Crosslinking agent> • Isocyanate-based crosslinking agent (Covestro Corporation, "Desmodule L-75")

[0152] <Pigments> • Black pigment (carbon black, manufactured by Toyo Color Co., Ltd., "Multi-Rack A903")

[0153] (Example 1) (1) Production of (meth)acrylic copolymer Ethyl acetate was added to the reaction vessel as a polymerization solvent, and after bubbling with nitrogen, the reaction vessel was heated while introducing nitrogen to initiate reflux. Subsequently, a polymerization initiator solution prepared by diluting 0.1 parts by mass of azobisisobutyronitrile 10-fold with ethyl acetate was added to the reaction vessel as a polymerization initiator. 94.9 parts by mass of n-heptyl acrylate containing bio-derived carbon, 0.1 parts by mass of 2-hydroxyethyl acrylate containing bio-derived carbon, and 5.0 parts by mass of acrylic acid were added dropwise over 2 hours. After the dropwise addition was complete, a polymerization initiator solution prepared by diluting 0.1 parts by mass of azobisisobutyronitrile 10-fold with ethyl acetate was added again to the reaction vessel, and the polymerization reaction was carried out for 4 hours to obtain a solution containing (meth)acrylic copolymer. The obtained (meth)acrylic copolymer-containing solution was diluted 50-fold with tetrahydrofuran (THF), and the resulting dilution was filtered through a filter (material: polytetrafluoroethylene, pore diameter: 0.2 μm) to prepare the measurement sample. This measurement sample was supplied to a gel permeation chromatograph (Waters, "2690 Separations Module"), and GPC measurement was performed under conditions of sample flow rate 1 mL / min and column temperature 40°C. The polystyrene-equivalent molecular weight of the acrylic copolymer was measured to obtain the weight-average molecular weight and polydispersity. The results are shown in Table 1.

[0154] (2) Preparation of adhesive composition To the obtained (meth)acrylic copolymer-containing solution, 15 parts by mass of tackifying resin A, 10 parts by mass of tackifying resin B, 10 parts by mass of tackifying resin C, and an isocyanate-based crosslinking agent were added so that the solid content of the crosslinking agent was 2.6 parts by mass, relative to 100 parts by mass of the acrylic copolymer in the (meth)acrylic copolymer-containing solution, to prepare adhesive composition 1.

[0155] (3) Manufacturing of adhesive tape The obtained adhesive composition 1 was applied to the release layer (the surface with a ridged pattern) of separator A shown in Table 2, so that the thickness of the adhesive layer after drying was 19 μm. It was then dried at 110°C for 5 minutes to form an adhesive layer having a grooved pattern that fits into the ridged pattern of separator A. Similarly, the adhesive composition 1 shown in Table 2 was applied to the release layer of separator F shown in Table 2, so that the thickness of the adhesive layer after drying was 19 μm. It was then dried at 110°C for 5 minutes to form an adhesive layer. Then, a substrate as shown in Table 2 was prepared, and an adhesive layer formed on separator A was bonded to one side of the substrate, and an adhesive layer formed on separator F was bonded to the other side. After curing at 40°C for 48 hours, a separator-attached adhesive tape was obtained, which has a substrate and separators on both sides of the adhesive tape.

[0156] (4) Measurement of the gel fraction of the adhesive layer Each formed adhesive layer was cut into a flat rectangular shape with a width of 20 mm and a length of 40 mm, and then the separator was peeled off to prepare test specimens. The prepared test specimens were immersed in ethyl acetate at 23°C for 24 hours, then removed from the ethyl acetate and dried at 110°C for 1 hour. The mass of the dried test specimens was measured, and the gel fraction (mass %) was calculated using the following formula (i), with W0=0. The results are shown in Table 1. Gel fraction (mass %) = 100 × (W2 - W0) / (W1 - W0) (i) (W0: Mass of the substrate, W1: Mass of the test specimen before immersion, W2: Mass of the test specimen after immersion and drying)

[0157] (5) Measurement of the shear storage modulus of the adhesive layer at 23°C and the shear storage modulus of the adhesive layer at 85°C The adhesive layer of the obtained separator-equipped adhesive tape was extracted by scraping it with a utility knife. The extracted adhesive layers were stacked to create a laminate consisting only of adhesive layers with a thickness of 1 mm, and this laminate was cut to a width of 6 mm and a length of 10 mm to prepare test specimens. Dynamic viscoelasticity measurements were then performed on the prepared test specimens using a dynamic viscoelasticity measuring device (DVA-200, manufactured by IT Measurement Control Co., Ltd.) in shear mode under nitrogen atmosphere, with a measurement temperature range of -40°C to 200°C, a heating rate of 5°C / min, a frequency of 10 Hz, and a strain of 0.08%. The shear storage modulus (Pa) of the adhesive layer at 23°C and 85°C was obtained, respectively. The results are shown in Table 1.

[0158] (6) Measurement of the glass transition temperature of the adhesive layer The adhesive layer of the obtained separator-equipped adhesive tape was extracted by scraping it with a utility knife. The extracted adhesive layers were stacked to create a laminate consisting only of adhesive layers with a thickness of 1 mm, and this laminate was cut to a width of 6 mm and a length of 10 mm to prepare test specimens. Dynamic viscoelasticity measurements were then performed on the prepared test specimens using a dynamic viscoelasticity measuring device (DVA-200, manufactured by IT Measurement Control Co., Ltd.) in shear mode under nitrogen atmosphere conditions, with a measurement temperature range of -40°C to 200°C, a heating rate of 5°C / min, a frequency of 10 Hz, and a strain of 0.08%. The glass transition temperature of the adhesive layer was obtained by reading the resulting dynamic viscoelasticity spectrum. The results are shown in Table 1.

[0159] (7) Measurement of the peeling force when the double-sided separator is peeled 180° from the adhesive tape. The obtained adhesive tape with separator was cut to a size of 50 mm wide x 100 mm long. After peeling off the separator F, a 50 μm thick PET film (Toyobo Co., Ltd., "E5200#50") was backed onto the exposed adhesive layer by running a 2 kg rubber roller back and forth once at a speed of 20 mm / s to prepare a test specimen. Then, using a tensile testing machine (Shimadzu Corporation, "Autograph AGS-X") in accordance with JIS Z 0237:2009, a peel test was performed on the prepared test specimens at 23°C and a peeling speed of 300 mm / min. Separator A was peeled off the adhesive tape at a 180° angle, and the peeling force of separator A at a 180° angle from the adhesive tape was measured. Separator F was also peeled at a 180° angle from the adhesive tape using the same method, and the similarities and differences in peeling forces at a 180° angle from the adhesive tape between separator A and separator F were confirmed, confirming that the peeling forces at a 180° angle from the adhesive tape were different. The results are shown in Table 2.

[0160] (Examples 2-6, 9, 11-13, 15-17, 19-20, Comparative Examples 1-4) An adhesive tape was obtained in the same manner as in Example 1, except that the types and amounts of monomers constituting the (meth)acrylic copolymer, and the types and amounts of each component of the adhesive composition were as shown in Table 1, and the types of separators and substrates were as shown in Tables 2 to 5. Various measurements were also performed in the same manner as in Example 1. The results are shown in Tables 1 to 5.

[0161] (Examples 7, 10, 14) Using the same method as described in "(3) Manufacturing of adhesive tape" above, an adhesive layer with the composition and thickness shown in Tables 2-3, formed on the separator shown in Tables 2-3, was bonded to one side of the substrate shown in Tables 2-3, and cured at 40°C for 48 hours to obtain a separator-attached adhesive tape having a substrate and having the adhesive layer and separator on only one side of the substrate. Various measurements were performed in the same manner as in Example 1. The results are shown in Tables 1 to 3.

[0162] (Example 8) Using the same method as described in "(3) Manufacturing of adhesive tape" above, a separator F was placed on top of an adhesive layer with the composition and thickness shown in Table 2, which was formed on separator A, and cured at 40°C for 48 hours to obtain a separator-attached adhesive tape that does not have a base material and has separators on both sides of the adhesive layer. Various measurements were performed in the same manner as in Example 1. The results are shown in Tables 1 and 2.

[0163] (Example 18) The adhesive composition 2 shown in Table 1 was stamp-printed onto the surface of the substrate shown in Table 4 in a cylindrical shape with a radius of 325 μm by a stamp printing manufacturer (Sankyo Kasei Kogyo Co., Ltd.), thereby forming an adhesive layer having the groove-like pattern shown in Table 4. Separator F was then superimposed on this groove-like adhesive layer. Furthermore, using the same method as described in "(3) Manufacturing of Adhesive Tape" above, an adhesive layer without a grooved pattern was formed on the separator F, having the composition and thickness shown in Table 4. This grooved-pattern-free adhesive layer was then bonded to the other side of a substrate on which an adhesive layer with a grooved pattern had been formed on one side. By curing at 40°C for 48 hours, a separator-attached adhesive tape was obtained, having a substrate and separators on both sides of the adhesive layer. Various measurements were performed in the same manner as in Example 1. The results are shown in Tables 1 and 4.

[0164] (Examples 21-22) An adhesive tape was obtained in the same manner as in Example 1, except that the types and amounts of each component in the adhesive composition were as shown in Table 1, and the types of separator and substrate were as shown in Table 4. Various measurements were also performed in the same manner as in Example 1. The results are shown in Tables 1 and 4.

[0165] The types of separators and substrates shown in Tables 2-5 are as follows: • Separator A: Paper embossed separator (K11 White PL(31)R-284 (Lintec Corporation)) • Separator B: Paper embossed separator (K8 white PL(63)TP R-384 (Lintec Corporation)) • Separator C: PET embossed separator (E7002 No. 80 (dot) (manufactured by Toyo Cloth Co., Ltd.)) • Separator D: PET embossed separator (E7002 No. 82 (manufactured by Toyo Cross Co., Ltd.)) • Separator E: PET embossed separator (9110JL (manufactured by MICHAELS)) • Separator F: PET separator (SP3000R (manufactured by Toyo Cross Co., Ltd.)) • Separator G: PET separator (PSPA101 (manufactured by Mitsubishi Chemical Corporation)) • Separator H: SP3000CE (manufactured by Toyo Cross Co., Ltd.) ·Base material A: Recycled PET base material (R-8250 (manufactured by Toyobo)) • Substrate B: Recycled PET substrate (Ecouse JF56 (manufactured by Toray Industries, Inc.)) ·Base material C: Recycled black PET base material (YA216 (manufactured by Nanya Corporation)) • Substrate D: Black polyimide substrate (GD050A (manufactured by PI Advanced Materials Co., Ltd.)) • Base material E: Polyurethane foam (Nipparei EXT-0.8t (manufactured by Nippon Hatsujo Co., Ltd.)) • Base material F: Polyurethane foam (Nipparei EXT-1.3t (manufactured by Nippon Hatsujo Co., Ltd.)) • Base material G: PET film (E5200 (manufactured by Toyobo Co., Ltd.))

[0166] [Table 1]

[0167] [Table 2]

[0168] [Table 3]

[0169] [Table 4]

[0170] [Table 5]

[0171] <Rating> The adhesive tapes with separators obtained in the examples and comparative examples were evaluated using the following method. The results are shown in Tables 6 to 9.

[0172] (Air release properties when applying adhesive tape) (1) Test 1 The resulting adhesive tape with separator was cut to a size of 25 mm in width and 100 mm in length. The separator on the adhesive layer side, where a groove-like pattern was formed, was peeled off, and the tape was placed on a glass plate with the adhesive layer in contact with it under conditions of 23°C. Then, it was pressed down once by rolling a 2 kg rubber roller back and forth at a speed of 20 mm / s, and the release of air at the adhesive interface was checked visually. Within a 25 mm × 100 mm area, if the area ratio of gas contamination was 5% or less, it was marked as "◎", if it was greater than 5% and 10% or less, it was marked as "○", if it was greater than 10% and 20% or less, it was marked as "△", and if it was greater than 20%, it was marked as "×".

[0173] (2) Test 2 (2-1) Confirmation of the pattern of the adhesive layer The resulting adhesive tape with separator was cut to a size of 25 mm in width and 100 mm in length. The separator on the adhesive layer side, which had a grooved pattern formed on it, was peeled off and replaced with a PET separator (Toyo Cloth Co., Ltd., "SP3000") measuring 25 mm in width, 100 mm in length, and 38 μm in thickness. A 2 kg roller was then pressed onto the adhesive layer at a speed of 20 mm / s for one back-and-forth motion, and the tape was left to stand for 10 minutes. The pattern of the adhesive layer was visually inspected. "○" indicated that the pattern of the adhesive layer was visible as before the separator replacement, "△" indicated that the pattern of the adhesive layer was visible but thinner than the pattern of the adhesive layer before the separator replacement, and "×" indicated that the pattern of the adhesive layer had disappeared and could not be inspected. Even if the pattern of the adhesive layer cannot be confirmed, if the "(2-2) Evaluation of air release properties" described later is "○" or "△", the resulting adhesive tape with separator can be used without any practical problems.

[0174] (2-2) Evaluation of air release properties Then, after peeling the replaced separator from the adhesive layer, adhesive tape was placed on the glass plate so that the exposed adhesive layer was in contact with it under conditions of 23°C. A 2kg roller was then passed back and forth once at a speed of 20mm / s, and air escape at the adhesive interface was visually checked. Within a 25mm x 100mm area, if the area ratio of gas contamination was 5% or less, it was marked as "◎", if it was greater than 5% but 10% or less, it was marked as "○", if it was greater than 10% but 20% or less, it was marked as "△", and if it was greater than 20%, it was marked as "×".

[0175] (3) Test 3 (3-1) Confirmation of the pattern of the adhesive layer The resulting adhesive tape with separator was cut to a size of 25 mm in width and 100 mm in length. The separator on the adhesive layer side, which had a grooved pattern formed on it, was peeled off and replaced with a PET separator (Toyo Cloth Co., Ltd., "SP3000") measuring 25 mm in width, 100 mm in length, and 38 μm in thickness. A 2 kg roller was then pressed onto the adhesive layer at a speed of 20 mm / s for one back-and-forth motion. A 200 g weight with a planar size larger than 25 mm in width and 100 mm in length was then prepared. The adhesive tape with the replaced separator was placed with the side of the replaced separator facing upwards, and the 200 g weight was placed on top of the separator. The tape was left undisturbed at 60°C for 24 hours. After air cooling to 23°C, the disappearance of the pattern was visually confirmed. If the adhesive layer pattern was visible as before the separator replacement, it was marked with "○". If the adhesive layer pattern could be confirmed but was thinner compared to the pattern before the separator replacement, it was marked with "△". If the adhesive layer pattern had disappeared and could not be confirmed, it was marked with "×". Even if the pattern of the adhesive layer cannot be confirmed, if the "(3-2) Evaluation of Air Release Performance" described later is "○" or "△", the resulting adhesive tape with separator will have excellent air release properties after being left to stand in a high-temperature environment. Furthermore, Test 3 evaluates air release performance after being left to stand in a high-temperature environment, and even if the pattern of the adhesive layer cannot be confirmed and the "(3-2) Evaluation of Air Release Performance" described later is "×", the resulting adhesive tape with separator can be used without any practical problems.

[0176] (3-2) Evaluation of air release properties After peeling the replaced separator from the adhesive layer, adhesive tape was placed on a glass plate under 23°C conditions so that the exposed adhesive layer was in contact with it. A 2kg roller was then passed back and forth once at a speed of 20mm / s, and air escape at the adhesive interface was visually checked. Within a 25mm x 100mm area, if the area ratio of gas contamination was 5% or less, it was marked as "◎", if it was greater than 5% but 10% or less, it was marked as "○", if it was greater than 10% but 20% or less, it was marked as "△", and if it was greater than 20%, it was marked as "×".

[0177] In the examples and comparative examples, those that did not receive a "×" in the evaluation results for Test 1 and Test 2 exhibit excellent air release properties when bonding adhesive tapes. Furthermore, Test 3 evaluates air release properties after being left to stand in a high-temperature environment. Even if this evaluation is "×", depending on the application, the adhesive tapes may exhibit excellent air release properties when bonding and can be used without practical problems.

[0178] [Table 6]

[0179] [Table 7]

[0180] [Table 8]

[0181] [Table 9] [Industrial applicability]

[0182] According to the present invention, it is possible to provide an adhesive tape with a separator that offers excellent air release when adhesive tapes are bonded together.

Claims

1. The tape includes at least one separator and an adhesive layer, The adhesive layer has a groove-like pattern on the surface that contacts the separator. In the adhesive layer, when the depth of the grooves in the groove-like pattern on the surface in contact with the separator is x (μm) and the thickness of the adhesive layer in contact with the separator is y (μm), the adhesive layer satisfies the following relation (I) or relation (II). Adhesive tape with separator, characterized by the following features. (I) 0 < x ≤ 5, and x ≤ y ≤ 8x (II) 5 < x, and x ≤ y ≤ (11 / 5)x + 29

2. The adhesive tape includes at least one separator, an adhesive layer and a substrate, The adhesive layer has a groove-like pattern on the surface that contacts the separator. When the depth of the grooves in the groove-like pattern on the surface of the adhesive layer in contact with the separator is x (μm), and the thickness of the adhesive layer in contact with the separator is y (μm), the adhesive layer satisfies the following relation (I) or relation (II): The adhesive layer includes a portion that satisfies x = y. Adhesive tape with separator, characterized by the following features. (I) 0 < x ≤ 5, and x ≤ y ≤ 8x (II) 5 < x, and x ≤ y ≤ (11 / 5)x + 29

3. The pitch of the groove-like pattern in the adhesive layer is greater than 0 μm and less than or equal to 3000 μm. The depth of the grooves in the groove-like pattern of the adhesive layer is greater than 0 μm and 40 μm or less. The width of the grooves in the groove-like pattern of the adhesive layer is 5 μm or more and 200 μm or less. Adhesive tape with separator according to claim 1 or 2.

4. The tape includes at least one separator and an adhesive layer, The separator has a ridged pattern on the surface that is in contact with the adhesive layer. When the height of the protrusions in the ridge-like pattern on the surface of the separator in contact with the adhesive layer is z (μm), and the thickness of the adhesive layer in contact with the separator is y (μm), the following relation (III), relation (IV), or relation (V) is satisfied. Adhesive tape with separator, characterized by the following features. (III) 0 < z ≤ 3, and (1 / 2)z ≤ y ≤ (20 / 3)z (IV) 3 < z ≤ 20, and (1 / 2)z ≤ y ≤ (53 / 15)z + 9.4 (V) 20<z and z-10≦y≦(53 / 15)z+9.4

5. The pitch of the ridge-like pattern of the separator is greater than 0 μm and less than or equal to 3000 μm. The height of the protrusions in the ridge-like pattern of the separator is greater than 0 μm and 40 μm or less. The width of the protrusions in the ridged pattern of the separator is 5 μm or more and 200 μm or less. Adhesive tape with separator according to claim 4.

6. Furthermore, the adhesive tape with separator according to claim 4 or 5 satisfies the following relational expression (VI). (VI)z≦y≦2z

7. The adhesive layer is a layer formed using an adhesive composition, The aforementioned adhesive composition contains a base polymer, The adhesive composition contains a (meth)acrylic copolymer having constituent units derived from alkyl (meth)acrylate, The gel fraction of the adhesive layer is 20% by mass or more. Adhesive tape with separator according to claim 1, 2, 4, or 5.

8. The (meth)acrylic copolymer has constituent units derived from alkyl (meth)acrylate having branched alkyl groups, The content of structural units derived from the branched alkyl group-containing alkyl (meth)acrylate in the (meth)acrylic copolymer is 50% by mass or more. Adhesive tape with separator according to claim 7.

9. The (meth)acrylic copolymer has constituent units derived from alkyl (meth)acrylate having an alkyl group with 4 to 8 carbon atoms, The content of constituent units derived from alkyl (meth)acrylate having an alkyl group having 4 to 8 carbon atoms in the (meth)acrylic copolymer is 50% by mass or more. Adhesive tape with separator according to claim 7.

10. The (meth)acrylic copolymer has constituent units derived from alkyl (meth)acrylate having an alkyl group with 6 to 8 carbon atoms, The content of structural units derived from alkyl (meth)acrylate having an alkyl group having 6 to 8 carbon atoms in the (meth)acrylic copolymer is 50% by mass or more. Adhesive tape with separator according to claim 7.

11. The adhesive tape with separator according to claim 10, wherein the (meth)acrylic copolymer has two or more constituent units derived from alkyl (meth)acrylate having an alkyl group with 6 or more carbon atoms and 8 or fewer carbon atoms.

12. The (meth)acrylic copolymer has constituent units derived from alkyl (meth)acrylate having a boiling point of 170°C or higher, as described in claim 7, with a separator adhesive tape.

13. The adhesive tape with separator according to claim 7, wherein the (meth)acrylic copolymer has constituent units derived from alkyl (meth)acrylate, which has a glass transition temperature (Tg) of -70°C or higher when it is a homopolymer.

14. The (meth)acrylic copolymer has constituent units derived from biological alkyl (meth)acrylates as described in claim 7, with a separator adhesive tape.

15. The (meth)acrylic copolymer has constituent units derived from monomers having crosslinkable functional groups, The content of constituent units derived from the monomer having the crosslinkable functional group in the (meth)acrylic copolymer is 0.01% by mass or more and 20% by mass or less. Adhesive tape with separator according to claim 7.

16. The (meth)acrylic copolymer has constituent units derived from hydroxyl group-containing monomers, The content of the constituent units derived from the hydroxyl group-containing monomer in the (meth)acrylic copolymer is 0.01% by mass or more and 2.0% by mass or less. Adhesive tape with separator according to claim 15.

17. The (meth)acrylic copolymer has constituent units derived from carboxyl group-containing monomers, The content of the constituent units derived from the carboxyl group-containing monomer in the (meth)acrylic copolymer is 0.1% by mass or more and 15% by mass or less. Adhesive tape with separator according to claim 15.

18. The (meth)acrylic copolymer has a weight-average molecular weight of 300,000 or more and 1,500,000 or less, and a polydispersity of 7.0 or less, as described in claim 7, for the adhesive tape with separator.

19. The aforementioned adhesive composition further contains a crosslinking agent, The amount of the crosslinking agent relative to 100 parts by mass of the base polymer is 0.01 parts by mass or more and 10 parts by mass or less. Adhesive tape with separator according to claim 7.

20. The adhesive tape with separator according to claim 19, wherein the crosslinking agent comprises at least one selected from the group consisting of isocyanate-based crosslinking agents and epoxy-based crosslinking agents.

21. The aforementioned adhesive composition further contains a tackifying resin, The content of the tackifying resin relative to 100 parts by mass of the base polymer is 10 parts by mass or more and 50 parts by mass or less. Adhesive tape with separator according to claim 7.

22. The adhesive tape with separator according to claim 21, wherein the tackifying resin has a softening point of 80°C or more and 170°C or less.

23. The adhesive tape with separator according to claim 21, wherein the tackifying resin comprises a tackifying resin having a hydroxyl value of 20 mg KOH / g or more and 150 mg KOH / g or less.

24. The separator-equipped adhesive tape according to claim 1, 2, 4, or 5, wherein the thickness of at least one of the adhesive layers is 120 μm or less.

25. The adhesive tape with separator according to claim 1, 2, 4, or 5, wherein the adhesive layer has a shear storage modulus at 23°C measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz of 0.1 MPa or more.

26. The adhesive tape with separator according to claim 1, 2, 4, or 5, wherein the adhesive layer has a shear storage modulus at 85°C measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz of 0.02 MPa or more.

27. The adhesive tape with separator according to claim 1, 2, 4, or 5, wherein the adhesive layer has a glass transition temperature of 0°C or higher, as measured by dynamic viscoelasticity measurement at a measurement frequency of 10 Hz.

28. The separator-equipped adhesive tape according to claim 1, 2, 4, or 5, wherein the separator comprises at least one selected from the group consisting of paper and film.

29. The separator has a resin layer having a ridged pattern, The resin layer is a layer containing polyethylene. Adhesive tape with separator according to claim 1, 2, 4, or 5.

30. The adhesive tape has the separator on both sides, The peeling force obtained by peeling one separator 180° from the adhesive tape is different from the peeling force obtained by peeling the other separator 180° from the adhesive tape. Adhesive tape with separator according to claim 1, 2, 4, or 5.

Citation Information

Patent Citations

  • Thermally conductive adhesive tape, article and image display device

    JP2015021067A

  • Base material for heat-resistant adhesive tape and heat-resistant adhesive tape composed of the same

    JP2015052050A

  • Double-sided adhesive sheet

    JP2015120876A